Promoting the terminal zero-pollution goal of hydrogen fuel cell vehicles: A stochastic evolutionary game analysis - Dan Zhao; Ya Zhang; Ye-kai Li; He-ping Wang; Jin-huan Tang; Jian Wang (Fuel, 2026)

Perillaldehyde reduces mitochondrial oxidative stress damage by regulating KCNT2/NR1D1 protein activity in vascular dementia rats - Qian-qian Wang; Hong-dou Zhang; Pei-yao Liu; Chun-rui Zhang; Bao-yue Cui; Xi-yue Li; Meng-yao zhao; Jin-he Yang; Peng Li; Ya-ling Yin; Xue-yu Sun (Molecular Biology Reports, 2026)

Shikonin alleviates high-fat diet-induced vascular aging and dysfunction by inhibiting oxidative stress and mitochondrial damage - Guang-qiu Ren; Hui-jun Liu; Ya-qi Guo; Mei-ling He; Jiao Li; Zhan-xia Li; Chen-hui Jia; Tong Liu; Jing Yang (Molecular Biology Reports, 2026)

Antioxidant Activity of Bioactive Peptides Derived from Ulva prolifera in HaCaT Cells and Zebrafish - Li-Ru Hong; Shuo-Qi Wang; Ting-Ting Wu; Zhi-Ru Chen; Mo Chen; Chun-Er Cai; Pei-Min He; Ya Zhao; Rui Jia (Marine Biotechnology, 2026)

Development of an in situ binding (ISB) method to evaluate the binding of Cry1Ac toxin to the larval midgut epithelium of Helicoverpa armigera - Qiming Sun; Fang Guan; Huiwen Shen; Kaixia Li; Yihua Yang; Ya-Zhou He; Yidong Wu (Pesticide Biochemistry and Physiology, 2026)

Residential greenness and incident type 2 diabetes: A large prospective cohort study in China integrating evidence from 17 global cohorts - Jian-Cheng Jiang; Chuan-Jiang He; Ai-Min Xu; Lu Wang; Xiao-Qi Zhu; Bei-Bei Li; Wen Liu; Ya Qiu; Jing-Ran Xu; Min-Hui Li; Zhuo-Hao Wang; Xiao-Guang Zou; et al. (Environmental Research, 2026)

D–A–A engineered covalent organic frameworks for photocatalytic degradation of microcystin-LR and inactivation of Microcystis aeruginosa - Niao Fu; Qingzhi Liu; Ya Zou; Yujiao Liu; Anzhong Peng; Vadim Popkov; Junfeng Li; Kezhen Qi; Jieli He (Chemical Engineering Journal, 2026)

Regulation mechanism of N2O and CH4 emissions during the pig manure composting amended with Polygonum Multiflorum Thunb - Ya-jun Duan; Hong-sheng Wu; Jiang-yu Yang; Zheng-tong Zhou; Tao-ran Shi; Cheng Cheng; Zhen-wei Li; Chun-fa Wu; Ming-chun Di; Yu-dong He; Feng-yi Hu (World Journal of Microbiology and Biotechnology, 2026)

Microcystin-LR induces dopaminergic neurodegeneration by MyD88-dependent neuroinflammation in zebrafish (Danio rerio) - Ya He; Kang Ou-Yang; Hui Yang; Liangmou Wang; Mengya Li; Dapeng Li; Li Li (Journal of Hazardous Materials, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Colloidally stable rice protein-carboxymethyl cellulose complexes tailoring high-protein liquids - Ren Wang; Xiaoyu Huang; Jian He; Wei Feng; Ya'’nan Li; Tao Wang (Food Chemistry, 2026)

Dopamine-coated LTO particles immobilized in PVA with directional dendritic channels for fast and selective lithium capture from salt-lake brines - Xunshuang Zhang; Yiming Hua; Mengyu Xie; Yihan Guo; Shilei Zhu; Yu He; Junxiang Wu; Shusen Chen; Zhou Song; Ya Nan Ye; Liangbin Li (Desalination, 2026)

Macroporous polyamidoxime particles with tunable cyclization functionalization via a swelling-restricted pore-locking preservation strategy for efficient uranium extraction from seawater - Junxiang Wu; Yu He; Xunshuang Zhang; Hongguang Mo; Yi Nan Wang; Shusen Chen; Zhou Song; Ya Nan Ye; Liangbin Li (Chemical Engineering Journal, 2026)

Seawater mixing as a mechanism to enrich gold ore: Insights from the Ludousou gold deposit (China) - Hao-Cheng Yu; Jun Deng; Kun-Feng Qiu; A. E. Williams-Jones; Ya-Qi Huang; Lian Zhang; Lei Wang; Ke Geng; Xiao-Fei Yu; Deng-Yang He; Jia-Dong Ma; Yong-Sheng Li (Mineralium Deposita, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Histone lactylation inhibits Slc25a51 expression and thus promotes collagen dysregulation of pelvic organ prolapse through impairing mitochondrial NAD+ transport - Yong He; Cheng Liu; Bingshu Li; Shasha Hong; Jianming Tang; Guotao Huang; Lian Yang; Mao Chen; Shufei Zhang; Ya Xiao; Jianfeng Liu; Minqi Ning; et al. (Science China Life Sciences, 2026)

Daucosterol linoleate from sweet potato inhibits breast cancer metastasis via SCD1 downregulation and suppression of epithelial-mesenchymal transition - Xintong He; Juan Li; Jun Lu; Zhaomin Chen; Ya Wang; Kehui He; Xuegang Li; Hang Ma; Xiaoli Ye (Human Cell, 2026)

Undescribed triterpenoid ellagitannins from Castanopsis calathiformis and their potential antiproliferative and hypoglycemic activity - Ya-feng Wang; Ying-rong Bao; Rui-jie He; Nao Pang; Zhang-bin Liu; Bing-yuan Yang; Gui-qin Li; Yong-lin Huang (Phytochemistry, 2026)

Plate bridge damage identification based on contact point response of vehicle-bridge system - Wen-Yu He; Jin-Tong Su; Yong-An Wang; Ya-Hui Shao; Dan Li (Engineering Structures, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

In vitro nephroprotective indolizidine alkaloids from marine-derived Streptomyces sp. KIB629 - Xiaowei Guo; Lei Wang; Xin He; Bing-Yi Xu; Jun-Jie Zhang; Jian-Ping Huang; Wei Li; Sheng-Xiong Huang; Jing Yang; Ya-Tuan Ma (Natural Product Research, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Soil texture modulates the impact of biodegradable microplastics on N2O emissions in agroecosystems - Ya Li; Fengxiao Zhu; Zhuyao Hua; Xiaomei Wang; Sha Chang; Changyin Zhu; Shiyin Li; Huan He; Cheng Gu (Journal of Hazardous Materials, 2026)

Freeze-casting polyamidoxime-based membrane adsorbents with synergistically enhanced mechanical properties and adsorption performance for uranium extraction from seawater - Yu He; Yanran Lu; Beibei Kang; Junxiang Wu; Xunshuang Zhang; Shilei Zhu; Zizhou Xu; Shusen Chen; Zhou Song; Ya Nan Ye; Liangbin Li (Journal of Environmental Chemical Engineering, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Environmental heat and cold stress, thyrotropin abnormalities, and reduced fecundability in 14 million Chinese couples: A nationwide preconception cohort study - Xinghou He; Mengyao Li; Ying Yang; Xinyi Lv; Hongbing Xu; Bin Zhang; Long Wang; Chuanyu Zhao; Jiahui Liu; Yuan He; Jianbing Wu; Xinghua He; et al. (Environmental Research, 2026)

Challenges in using platform carbonates to trace global seawater δ13C variations: A review and insights from terminal Ediacaran carbonate platforms - Yi Ding; Ya Zhang; Shugen Liu; Gang Zhou; Huaguo Wen; Daizhao Chen; Wei Yan; Caijun Lan; Yu He; Chao Deng; Zhiwu Li (Earth-Science Reviews, 2026)

Unveiling the key role of COF matrices in enhancing the OER performance of single-atom catalysis through electronic modulation - Zihan Wang; Chunyang Li; Ya Xu; Weiqiang Wei; Yanchao Bi; Yan He; Huifang Li (Chemical Engineering Journal, 2026)

Antimicrobial resistance analysis of Escherichia coli isolated from foxes in China - Hao Ni; Jiagong Hou; Qing-Yu Hou; Chao Xu; Xue Leng; Xue-Min Li; Ya Qin; Shuo Liu; Meng-Ting Yang; Lu-Yao Tang; Yu-Zhe Sun; Quan Zhao; et al. (Veterinary Research Communications, 2026)

Efficient combined use of electroacupuncture with ordered collagen scaffolds enhances the therapeutic efficacy of human spinal cord-derived neural progenitor cells therapy in spinal cord injury rats - Yunlong Zou; Weiwei Xue; Bo Guo; Lu Li; Yannan Zhao; Xianming Wu; Zhifeng Xiao; Qi Zhang; Dezun Ma; Xinhao Zhao; Bing Chen; He Shen; et al. (Science China Life Sciences, 2026)

Text mining and machine learning based health risk prediction for soil polycyclic aromatic hydrocarbons at typical coal-fired industrial sites in china - Lu Han; Hanyuan Gu; Mengfang Chen; Zhanfei He; Yufei Jia; Yudong Feng; Jing Li; Ya Zhu; Ye zou (Journal of Hazardous Materials, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

AtGASA1 positively regulates Arabidopsis response to salt stress by suppressing accumulation of reactive oxygen species - Jian-Bo Song; Hao-En He; Cai-Feng Wang; Xian-Zhi Zuo; Zi-Xin Zhao; Ya-Ru Li; Yu-Fan Chen; Shu-Fan Liu; Han-Wen Guo; Xuan Huang (Plant Cell Reports, 2026)

Contrasting effects of microplastics on N2O emission and denitrifiers in two agricultural soils - Fengxiao Zhu; Aoyu Zhou; Yuqing Ding; Haojie Wang; Sha Chang; Ya Li; Huan He (Applied Soil Ecology, 2026)

Early Cretaceous radiolarian assemblages in mélange of Yarlung-Tsangpo suture zone in the Saga area, southern Xizang - Zhi-Hao He; Xin Li; Ya-Lin Li; Atsushi Matsuoka; Hui Luo; Xiao-Hui Cui; Jian-Bo Cheng (Palaeoworld, 2026)

Harpin Protein Treatment Makes a Positive Impact on Maintaining the Postharvest Quality of Strawberry Fruits - Hao Li; Zihang Ouyang; MuSha She; ManTong Zhao; CaiXia He; Haoru Tang; Ya Luo (Journal of Plant Growth Regulation, 2026)

Histomorphological analysis of the relationship between Helicobacter pylori infection of the gastric mucosa and host immunity strength - Yang-kun Wang; Quan-wei Guo; Hai-ying He; Ying-ying Li; Chao-ya Zhu; Ping Li; Bo Jiang; Su-nan Wang; Si-liang Xu (Journal of Molecular Histology, 2026)

Intelligent stratigraphic identification based on real-time construction parameters from rotary drilling rigs - Chao-Ji Li; He Yang; Fei Ren; Hong-Ya Yue; Xiu-Guang Song; Li-Min Li; Pei-Zhi Zhuang (Bulletin of Engineering Geology and the Environment, 2026)

Ecological risk analysis and prediction of microplastics' effects on Microcystis aeruginosa in freshwater system: a meta-analysis approach - Liangmou Wang; Ya He; Hui Yang; Mengya Li; Dapeng Li; Li Li (Environmental Pollution, 2026)

Behaviorally inspired by blue-whale throat-pleats during filter feeding: A thermoresponsive hydrogel for achieving efficient solar-driven cyclic water release and purification - Yan-Shu Xiong; Mei Li; Tanli Lu; You-Ya Sun; Hai-Qin Lu; Wen Li; He Liu; Zhanqian Song (Chemical Engineering Journal, 2026)

Numerical Implementation of HSS Model for Horizontal Loading of a Jacket Foundation with Four Monopiles in Seabed - Jianhong Ye; Fuqin Yang; Kunpeng He; Ya Li (Journal of Marine Science and Engineering, 2026)
For geotechnical structures with a strict control requirement of deformation, the high modulus and non-linear attenuation characteristics of the surrounding soil under small-strain conditions cannot be ignored during performance evaluation; the HSS constitutive model offers significant advantages over conventional approaches (e.g., Mohr–Coulomb) to describe the above soil behaviors. In this study, the theoretical framework of the HSS model, i.e., the yield function, hardening laws, and flow rule, is first elucidated. Subsequently, it is numerically implemented into the finite element software FssiCAS. The reliability of the FssiCAS software (Version 3.5) incorporating the HSS model is validated through a triaxial test and a physical test involving the horizontal loading of the monopile. Finally, taking the four-monopile jacket foundation of an offshore wind turbine (OWT) in Lianjiang County, China, as a representative, the HSS model is adopted to describe the mechanical behaviors of a seabed foundation. The horizontal bearing characteristics of the jacket foundation–seabed system under multi-angle horizontal loading are investigated, and the influence of the horizontal loading angle on the horizontal bearing capacity, jacket displacement, and seabed deformation is quantitatively elucidated. The results indicate that (1) the horizontal bearing capacity of the jacket is minimal when horizontal loading is along the diagonal of the four piles, representing the most severe loading case, and therefore, the horizontal bearing capacity of the jacket foundation–seabed system should be evaluated based on this case; and (2) the FE software FssiCAS has good reliability when dealing with pile–soil interaction problems involving complex geometries and complex mechanical behaviors of seabed soils. This study could provide technical support and an analysis platform for the design of jacket foundations for complex marine structures, such as OWTs.

Valorization and detoxification of MSWI fly ash via carbonation-ultrasonication for a low-chlorine, high-calcium, and low-toxicity derivative - Xuyang He; Dingyuan Zhang; Jincheng Wang; Weihua Li; Xue Li; Yingjie Sun; Qingjian Zhang; Ying Zhu; Rongxing Bian; Weichen Xu; Xuexin Fu; Ya-nan Wang; et al. (Journal of Cleaner Production, 2026)

Effects of geographical origin, variety, harvest season, and their interactions on stable isotopes and multi-elements in tea - Xiao-Li Wang; Bo-Wen Zhang; Ya-Nan Wu; Yan-Bo Hao; Xue-Jiao Chen; He-Yuan Jiang; Hong-Yan Liu (Food Control, 2026)

Targeted photodynamic therapy for multispecies dental biofilms using liposome encapsulated p-Toluquinone - Chen Liang; Yongli Li; Zuan-Tao Lin; Zhilong Wang; Ya He; Yan Dong; Zihan Ran; Sophia Zhang; Ying Zhao; Songling Wang; Mei X. Wu (Chemical Engineering Journal, 2026)

Integrated physiological and multi-omics insights into Chlorella mutagenized by atmospheric and room temperature plasma for enhanced saline aquaculture wastewater treatment and bioresource production - Xiao-Ya Liu; Fan-Xing He; Tong-Chao Qu; Zhao-Hong Weng; Peng-Fei Li; Jie Ye; Hai-Yan Fu (Bioresource Technology, 2026)

Small-strain stiffness of in situ granite residual soil: Experimental comparison under biased and isotropic consolidation - Song Yin; Ya He; Sen Li; Siyue Zheng; Xianwei Zhang; Xinming Li (Soil Dynamics and Earthquake Engineering, 2026)

Quantitative prediction of fracture distribution in deep conglomerate reservoirs of the Bozhong 19-6 South structure, offshore Bohai Bay Basin, East China: Insights from numerical simulation of multiphase strike-slip regimes - Liang Zhou; Chao Deng; Li-ya Da; Yu Xia; He-wei Hu; Kai Ji; Chang-yu Fan; Yong Cheng; Yu-jie Ning; Xiao-fang Yang (Marine and Petroleum Geology, 2026)

Programmable and multi-stimuli responsive hydrogel actuator mediated by nanocellulose with intrinsic self-sensing capacity - Ya Lu; Shengnan Li; Fang Deng; Yiying Yue; Shuijian He; Shaohua Jiang; Mingqiang Ye; Yihui Zhou; Huining Xiao; Jingquan Han (Carbohydrate Polymers, 2026)

Exogenous proanthocyanidins improved postharvest quality and resistance to Botrytis cinerea infection of strawberry via enhanced non-enzymatic antioxidants accumulation and salicylic acid signaling pathway - Yuanxiu Lin; Ziqing Sun; Xiao Wang; Shuaipeng Cao; Yin Liu; Shuangyang Liu; Yunting Zhang; Mengyao Li; Qing Chen; Yong Zhang; Yan Wang; Wen He; et al. (Postharvest Biology and Technology, 2025)

Bioactive sesquiterpene lactones with cytotoxic activity from Youngia japonica - Hao Gong; Kuan Lin; Lei Zhang; Yi Huang; Li-Juan Hu; Xiao-Ya Liu; Hao Ming; Si-Qi Wang; Qing-Qin He; Xian-Sheng Ye; Shu-Xiu Zhu (Phytochemistry Letters, 2025)

Trigger efficient peroxydisulfate-assisted photocatalysis by S-scheme Co3O4/BiOCl heterojunctions: Vital roles of Co2+/Co3+ redox centers and oxygen vacancies - Chang-Bin Yu; Chong Xu; Lin He; Wei-Ya Huang; Kai Yang; Dan Li (Journal of Environmental Chemical Engineering, 2025)

Non-optimum temperature exposure may impair cardiac structure and function: A repeated-measure analysis based on echocardiography - Xingyi Qiu; Yufei Cheng; Qinglin He; Ya Gao; Wenshu Li; Xiaowei Xue; Mengyuan Cheng; Renjie Chen; Gang Zhao; Xianhong Shu (Environmental Research, 2025)

Designing light-guiding carriers in microalgal-bacterial systems: From optimization to integration and development perspectives - Cong-Cong Tang; Jin-Qiao Liu; Yong-Qi Cheng; Ya-Ru Hu; Zhang-Wei He; Wen-Qiong Wang; Zhi-Hua Li; Xiaochang C. Wang; Yu Tian (Chemical Engineering Journal, 2025)

Research on the Mechanism of Complex Water-flooded Layers and Well Logging Evaluation Methods in the M Oilfield - Wen-Yuan He; Ya-Dong Wu; Li-Xiang Feng; Chang-Xi Li; Jin-Bin Wan; Guo-Hui Ni (Applied Geophysics, 2025)

Advanced strategies in organoid/organ-on-a-chip for food safety and nutrition - Yiyan Zhou; Feiran Wang; Rui Zhao; Tianyi Huang; Wentao Su; Ya Wen; Zhixian He; Dong Li (Food Research International, 2025)

Electrochemical and photoelectrochemical CO2 reduction to hydrocarbons by a copper-based molecular catalyst - Zhibing Wen; Rong Zhang; Yong Zhu; Hua Gao; Ran Zhao; Zhi Chen; Siyao Wang; Shuanglin He; Ya-Qiong Zhang; Rong-Zhen Liao; Fei Li (Chemical Engineering Journal, 2025)

Differential effects of size-specific PM components on stroke hospitalization in Northwest China's arid area - Huanhuan Wei; Ce Liu; Ya Xiao; Li He; Hao Zhao; Zhaoru Yang; Huan Chen; Ququmo Guoji; Bin Luo (Atmospheric Environment, 2025)

Dietary sodium butyrate and poly-β-hydroxybutyrate improve growth performance, intestinal antioxidant and non-specific immune functions and resilience from ammonia stress in grass carp (Ctenopharyngodon idella) - Yingying Wang; Kang Ou-Yang; Ya He; Hui Yang; Liangmou Wang; Dapeng Li; Li Li (Aquaculture International, 2025)

Separation and recovery of vanadium from leaching solution of calcium roasting vanadium slag by extraction with P204 extractant - Da-long Wang; Lin Zhang; Jing-wei Li; Chen Chen; Yin-he Lin; Zhi Yang; Da-ya Wang; Huan-jian Hou; Jian Chen; Tang-jie Zhou; Wen-ming Tang (Minerals Engineering, 2025)

Efficient degradation of dichloromethane by novel cell-immobilized-filled biotrickling filters: Performance and mechanisms - Yaxue He; Xiaoyan Li; Rui Han; Aohan Zhang; Ya Deng; Piet N.L. Lens; Christian Kennes; Zhao Huang; Jianmeng Chen; Guangfeng Yang; Dongzhi Chen (Journal of Hazardous Materials, 2025)

Efficient room-temperature hydrolytic cleavage of CS2 via Pd-anchored polynitrogen porous polymers - Kai-Wen Jiang; Xing-Yu Chen; Xiao-Li Jiang; Qing-Ya Sun; Yu-Peng Dai; Hui-Zhen He; Ying Zhou; Ping Shang; Xuan-Feng Jiang (Journal of Hazardous Materials, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

Proteome Profiling of Serum Reveals Pathological Mechanisms and Biomarker Candidates for Cerebral Small Vessel Disease - Yun-chao Wang; Hang-hang Zhu; Liu-Chang He; Ya-ting Yao; Lei Zhang; Xin-li Xue; Jing-yi Li; Li Zhang; Bo Song; Chang-he Shi; Yu-sheng Li; Yuan Gao; et al. (Translational Stroke Research, 2025)

Geniposide protects against cerebral ischemic injury by targeting SOX2/RIPK1 axis - Xiaogang He; Yi Zhang; Chunyang Xu; Rong Zhang; Ya Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Genomic characterization of Gillisia xinjiangensis sp. nov.: insights into nitrogen metabolism, stress adaptation, and application potential - Hao-hao Wang; Chi Zhang; Ya-qin Chen; Yi-fan Guo; Li-jian Ding; Sheng-fa Zhang; Gai-jun Du; Wei-yan Zhang; Shan He (Systematic and Applied Microbiology, 2025)

Acetamiprid mediates cognitive dysfunction through the gut-brain axis: Synaptic damage and immune-mediated blood-brain barrier dysfunction - Bing Wu; Xue-yan Tian; Wen-si Ni; Hao-Xuan Gao; Yu-wen Wang; Ling-he Zhang; Yu-bin Li; Yan-ling Lv; Ya-nan Song; Yu-cheng Yan; Xiao-zhe Geng; Yi-man Li; et al. (Journal of Hazardous Materials, 2025)

Comparative investigation of aroma characteristics of six chrysanthemum species based on sensory evaluation and multivariate statistical analysis to provide a strategy for the cultivation of sweet-scented chrysanthemums - Yi Li; Ya Pu; Fang Xu; Yajing Niu; Mengmeng Zhang; He Huang (Food Chemistry, 2025)

Preservation processes of liquid nitrogen spray freezing technology on Sebastes schlegelii in two stages of freezing and frozen storage: Focusing on changes in water status, protein characterization, texture properties and volatile compounds - Weijia Zhang; Zhuyu Yang; Wenjing Zhao; Lianfa Gong; Wentao Liu; He Xu; Lili Sun; Tingwei Zhang; Ya Li; Guiping Wang; Xinxing Xu; Yuanhui Zhao (Food Chemistry, 2025)

Effect of organic carbon enrichment on halogenated organic pollutants in wetland sediments of the Yellow River Estuary and Jiaozhou Bay, China - Zi-Cen Zuo; Shan-Shan Liu; Jie Ni; Ya-Li Cao; Zhen He; Gui-Peng Yang (Environmental Research, 2025)

Surface-enhanced fluorescence-encoded nanoprobes for contrast-enhanced single-cell imaging of gene expression - Lulu Song; Shuang Li; Chaojie Su; Ya Wang; Yifu Wang; Yiqiong Hu; Yamin Xiong; Leiliang He (Chemical Engineering Journal, 2025)

Allelopathic inhibition of Oocystis borgei on Microcystis aeruginosa: Mechanisms and identification of the predominant allelochemicals - Liangmou Wang; Ya He; Hui Yang; Qian Zhang; Dapeng Li; Li Li (Algal Research, 2025)

Metabolome and Genome Analysis of a Novel Endophytic Fungus Aureobasidium pullulans KB3: Discovery of Polyketones and Polyketone Biosynthesis Pathway - Shuai Wang; Jia-Nuo He; Ying-Jie Wang; Wen-Ya Zhao; Qing-Xia Yang; Ya-Na Wang; Yang Zhang; Li-Ping Zhang; Hong-Wei Liu (Biochemical Genetics, 2025)

Juvenile macular degeneration in nonhuman primates generated by germline knockout of ABCA4 gene - Ya Ma; Qiang Lin; Hai-Long He; Yi-Xin Liu; Min Li; Xiao-Hui Zhang; Zi-Bing Jin (Science Bulletin, 2025)

Demethylzeylasteral inhibits osteosarcoma cell proliferation by regulating METTL17-mediated mitochondrial oxidative phosphorylation - Jingyu Cao; Haotian Zhang; Chengbo Wang; Lihua He; Ya Li; Zimeng Wang; Xianxiao Li; Faisal Aziz; Minglei Yang; Xiangzhan Zhu (Toxicology and Applied Pharmacology, 2025)

Greenness, nighttime light, and couple fecundability: A national cohort study between 2014 and 2020 - Mengyao Li; Xinghou He; Bin Zhang; Hongbing Xu; Jianbin Wu; Xuyang Shan; Ya Zhang; Huiying Xu; Hongguang Zhang; Yuan He; Yan Fang; Zuoqi Peng; et al. (Environmental Research, 2025)

The sedimentological heterogeneities and responses to controlling factors in Toutunhe Formation of Xiayan Rise, Junggar Basin - Nai-xiang He; Xiang Li; Ya-jie Ding; Rui Qi; Gang Xu; Zi-jian Han; Chao Hou; Lei Xie (Applied Geophysics, 2025)

COP1 Overexpression Attenuates Nociceptive Behaviors and Neuroinflammation in Cancer-Induced Bone Pain by Suppressing c/EBPβ - Dan-Yang Li; Lin Liu; Shao-Jie Gao; Dai-Qiang Liu; Long-Qing Zhang; Jia-Yi Wu; Fan-He Song; Xin-Yi Dai; Ya-Qun Zhou; Wei Mei (Journal of Neuroimmune Pharmacology, 2025)

Poly (sodium acrylate-acrylamide) hydrogels for enrichment and purification of microalgal biomass in an open system: performance optimization and mechanistic analysis - Cong-Cong Tang; Yong-Qi Cheng; Sheng-Long Chen; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Journal of Environmental Management, 2025)

Elevated mercury wet deposition in the biodiversity hotspot of southwestern China - Xiaohui Li; Dan Hu; Mengjie Lei; Ya Tang; Xue Qiao; Lei He (Environmental Research, 2025)

Increased CO2 Concentration Mitigates the Impact of Nitrite on Zebrafish (Danio rerio) Liver and Gills - Xinyu Wang; Yao Tang; Hui Yang; Ya He; Kang Ou-Yang; Liangmou Wang; Qian Zhang; Dapeng Li; Li Li (Fishes, 2025)
Nitrite and carbon dioxide (CO2) are common environmental substances in intensive aquaculture ponds. However, the effects and mechanisms of their combined exposure on aquatic animals remain unclear. In this study, we investigated the toxic effects of 2.5, 5, and 10 mg/L CO2 in the presence of 2 mg/L nitrite on hematological, blood gas parameters, and liver physiological and pathological changes in zebrafish (Danio rerio) over 14 days and 28 days. Our results demonstrated a reduced nitrite uptake and accumulation in the gills and liver of zebrafish exposed to nitrite and varying levels of CO2. Increased CO2 levels also led to a decrease in the expression of gill ae1, whereas the transcriptional levels of nhe1 and nhe3b, nkcc and nbc1 were notably upregulated. Moreover, there was a decrease in Cl− and Na+ concentrations, along with an increase in K+ concentrations. These changes suggested that zebrafish responded to increased CO2 stress by reducing their absorption of chloride-dependent nitrite, excreting H+ and maintaining their internal pH. Exposure to higher CO2 levels in the presence of nitrite resulted in lower blood MetHb levels and liver oxidative stress compared to the nitrite single-exposure treatment. Furthermore, co-treatment with CO2 and nitrite attenuated the nitrite-induced damage to genes related to mitochondrial respiratory chain function (ndufs1, mtnd5, mtycb, atp5f1b, mtatp8), leading to elevated ATP levels. Exposure to nitrite alone increased the expression of lipolytic genes (hsla, cpt1aa, atgl) and decreased the expression of lipid synthesis genes (fasn, acaca), resulting in a decrease in TG and TC content in zebrafish liver. However, co-treatment with CO2 and nitrite prevented the nitrite-induced disruption of lipid metabolism, as evidenced by the improvement in TG and TC levels, as well as transcriptional levels of lipid metabolism-related genes. In conclusion, our study suggests that in the presence of 2 mg/L nitrite, increased CO2 (2.5–10 mg/L) may modulate ion transporter genes to reduce the chloride-dependent nitrite uptake and maintain pH homeostasis, concurrently alleviating oxidative stress, restoring mitochondrial respiratory function, and improving lipid metabolism in a dose-dependent manner. These changes may be related to the increase in the concentration of bicarbonate ions in the water as the CO2 level rises. These findings shed light on the potential protective effects of CO2 in mitigating the harmful effects of nitrite exposure in aquatic animals.

A review on the genus Melodinus: traditional uses, phytochemical diversity and pharmacological activities of indole alkaloids - Si-Fan Teng; Fang-Ru Li; Qi-Min Cui; Afsar Khan; Ting He; Xiao-Dong Luo; Ya-Ping Liu; Gui-Guang Cheng (Phytochemistry Reviews, 2025)

The antinociceptive and anti-alpha-glucosidase effects of glucosides from Hemiphragma heterophyllum Wall. - Chun-Fang Wen; Yu-Xiao Li; Ke-Xin Nie; Qiu He; Ya Lu; Zi-Liang Wang; Xi-Shan Bai; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2025)

Groundwater health risks and water quality assessment in the sources of many mighty rivers in Asia: Ngari, Tibet - Fei He; Shehong Li; Lian Song; Qiao Han; Dan Zeng Ya Jie; Yong Shui; Jen-How Huang (Process Safety and Environmental Protection, 2025)

The Arabidopsis heterotrimeric G protein α subunit binds to and inhibits the inward rectifying potassium channel KAT1 - Jiang-Fan Guo; Hui Zhou; Zhuo-Ran Hu; Ya-Lan Yang; Wen-Bin Wang; Yan-Ru Zhang; Xue Li; Nuerkaimaier Mulati; Ying-Xin Li; Lu Wu; Yu Long; Jun-Min He (Plant Science, 2025)

Targeted isolation of lignans and triterpenoids from kadsura coccinea by molecular networking and anti-RA-FLS activity - Shi-qi Liu; Qing-ling Xie; Ya-si Deng; Ling Liang; Han-wen Yuan; Bin Li; Huang-he Yu; Xing Tian; Yi-xing Qiu; Guy Paulin Kemayou Mouthe; Nuzhat Shehla; Ye Zhang; et al. (Phytochemistry, 2025)

Microcystin-LR induces fatty liver metabolic disease in zebrafish through the PPARα-NOD1 pathway: In vivo, in vitro, and in silico investigations - Kang Ou-Yang; Ya He; Hui Yang; Liangmou Wang; Qian Zhang; Dapeng Li; Li Li (Journal of Hazardous Materials, 2025)

Impact of eight extruded starchy whole grains on glycemic regulation and fecal microbiota modulation - Fang Fang; Yu-Xin He; Hao-Qiang Wang; Yan-Li Zhang; Ya-dong Zhong; Xiao-Tian Hu; Shao-Ping Nie; Ming-Yong Xie; Jie-Lun Hu (Food Hydrocolloids, 2025)

The MC-LR induced neuroinflammation and the disorders of neurotransmitter system in zebrafish (Danio rerio): Oxidative stress as a key - Ya He; Kang Ouyang; Hui Yang; Liangmou Wang; Qian Zhang; Dapeng Li; Li Li (Fish & Shellfish Immunology, 2025)

Is there an association between eye-level greenness and childhood hypertension using street view? Findings from the Seven Northeastern Cities study in China - Huang-Min Yang; Jing-Yao Wang; Cheng Li; Ya-Qin Zhang; Ruoyu Wang; Qi Yang; Yao Yao; Zilong Wang; Shu-Li Xu; He-Hai Huang; Qian-Sheng Hu; Ru-Qing Liu; et al. (Environmental Research, 2025)

Innovative coupling pathway for second- and third-generation biomass: Efficient L-lactate synthesis from xylose and C1 compounds - Ya Wu; Gen Lu; Ruiqi Zeng; Zeyang Li; Xin Xu; Yifan Gui; Chonghao Guo; Lizhen Deng; Yutong Bie; Derui Zhang; Yuxin He; Yuyang He; et al. (Chemical Engineering Journal, 2025)

Embedded solar-powered hydrogel evaporator for enhancing uranium extraction from seawater - Zhenglin Wang; Yuanyuan Li; Feng Liu; Huibo Shao; Ya’nan Yang; Liru Wang; Zifeng Jin; Dan Li; Xiaojun He; Nan Chen (Chemical Engineering Journal, 2025)

Genome-wide characterization and comparative transcriptomics unravel CpMADS47 as a positive regulator during fruit ripening and softening in Chinese cherry - Tai Tian; Shiqing Yin; Fengting Huang; Longqiang Feng; Yan Ma; Hao Wang; Jing Zhang; Wen He; Yuanxiu Lin; Yunting Zhang; Mengyao Li; Zhiwei Wu; et al. (Postharvest Biology and Technology, 2025)

Structural characterization and proteomic profiling of oviposition secretions across three rice planthopper species - Jia-Bao Lu; Peng-Peng Ren; Ying Tian; Yan-Yan Yang; Qing-Kai Feng; Xiao-Ya Zhang; Fang He; Hai-Jian Huang; Jian-Ping Chen; Jun-Min Li; Chuan-Xi Zhang (Insect Biochemistry and Molecular Biology, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Desertibaculum subflavum gen. nov., sp. nov., a novel member of the family Sneathiellaceae isolated from the Kumtag Desert soil - Chu-Ying Feng; Huan-Huan He; Shuai Li; Zhuo-Huan Zheng; Yi-Jun Mo; Wen-Hui Lian; Chun-Yan Lu; Dong-Ya Zhang; Wen-Jun Li; Lei Dong (Antonie van Leeuwenhoek, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Response of the algal-bacterial community to thermal stratification succession in a deep-water reservoir: Community structure, co-assembly patterns, and functional groups - He Lv; Meng Yang; Ya Cheng; Kai Li; Tinglin Huang; Gang Wen (Environmental Research, 2024)

Disentangling the assembly patterns and drivers of microbial communities during thermal stratification and mixed periods in a deep-water reservoir - He Lv; Meng Yang; Ya Cheng; Kai Li; Gang Ji; Tinglin Huang; Gang Wen (Science of The Total Environment, 2024)

Deciphering the effects of different types of high-temperature Daqu on the fermentation process and flavor profiles of sauce-flavor Baijiu - Wei Shi; Li-Juan Chai; Han Zhao; Ya-Ning Song; Jun-Lan Mei; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Bo Yang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Bioscience, 2024)

Promoting symbiotic relationship between microalgae and bacteria in wastewater treatment processes: Technic comparison, microbial analysis, and future perspectives - Cong-Cong Tang; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Chemical Engineering Journal, 2024)

Paleozoic orogenic gold mineralization from metamorphism of volcanic sequences in the North Qinling terrane (central China): Insights from the Yindongpo gold deposit in the Tongbai area - Ming-Chun Chai; Jian-Wei Li; Ya-Fei Wu; Xiao-Ping Xia; Huai-Yu He; Wei Fu (Mineralium Deposita, 2024)

Influence of Chinese herbal plants on greenhouse gas emissions from pig manure composting and fermentation - Ya-jun Duan; Hong-sheng Wu; Guang-yao Chen; Feng-yi Hu; Yan-hui Li; Zhen-wei Li; Jin-he Chi; Dong-ming Lu; Xiao-ming Gu; Ming-chun Di (International Biodeterioration & Biodegradation, 2024)

Design and synthesis of ligustrazine derivatives as potential anti-Alzheimer’s agents - Xu-fei Chen; Shan-shan Li; Yu-jun Bai; Ze-feng Zhao; Ya-jun Bai; Gu Gong; Xi-rui He; Xiao-hui Zheng (Natural Product Research, 2024)

Synergistic solidification and mechanism research of electrolytic manganese residue and coal fly ash based on C-A-S-H gel material - Bo Liu; Bo Yue; Li-li He; Bang-bang Meng; Ya-xin Wang; Tao Wang; Hong Gao (Journal of Environmental Management, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Electrocatalytic nitrogen reduction to ammonia at low overpotentials based on tungsten carbide doped by non-precious metal single cobalt atoms - Ya Gao; Meng-Jiao Zhu; Xian-He Liu; Guo-Liang Dai; Yi-Wen Zhou; Ze-Da Meng; Li Luo; Tian Gan; Feng Chen; Yu-Yang Zhou; Wen-Wen Deng; Shou-Qing Liu (Chemical Engineering Journal, 2024)

Nitrite induces hepatic glucose and lipid metabolism disorders in zebrafish through mitochondrial dysfunction and ERs response - Hui Yang; Kang Ou-Yang; Ya He; Xinyu Wang; Liangmou Wang; Qing Yang; Dapeng Li; Li Li (Aquatic Toxicology, 2024)

Placenta-targeted Treatment Strategies for Preeclampsia and Fetal Growth Restriction: An Opportunity and Major Challenge - Jianjian Cui; Zejun Yang; Ruilin Ma; Wencong He; Hui Tao; Ya’nan Li; Yin Zhao (Stem Cell Reviews and Reports, 2024)
The placenta plays a crucial role in maintaining normal pregnancy. The failure of spiral artery remodeling (SAR) is a key factor leading to placental ischemia and poor perfusion which is strongly associated with obstetric diseases, including preeclampsia (PE) and fetal growth restriction (FGR). Existing interventions for PE and FGR are limited and termination of pregnancy is inevitable when the maternal or fetus condition deteriorates. Considering the safety of the mother and fetus, treatments that may penetrate the placental barrier and harm the fetus are not accepted. Developing targeted treatment strategies for these conditions is urgent and necessary. With the proven efficacy of targeted therapy in treating conditions such as endometrial cancer and trophoblastic tumors, research on placental dysfunction continues to deepen. This article reviews the studies on placenta-targeted treatment and drug delivery strategies, summarizes the characteristics proposes corresponding improvement measures in targeted treatment, provides solutions for existing problems, and makes suggestions for future studies. Graphical abstract

Long-term polystyrene nanoparticles exposure reduces electroretinal responses and exacerbates retinal degeneration induced by light exposure - Jincan He; Shiyi Xiong; Wenchuan Zhou; Hao Qiu; Yuqing Rao; Ya Liu; Guiyan Shen; Peiquan Zhao; Guangquan Chen; Jing Li (Journal of Hazardous Materials, 2024)

Differential associations of fine and coarse particulate air pollution with cause-specific pneumonia mortality: A nationwide, individual-level, case-crossover study - Ye Zhang; Qinglin He; Xunliang Tong; Peng Yin; Yunning Liu; Xia Meng; Ya Gao; Su Shi; Xinyue Li; Haidong Kan; Maigeng Zhou; Yanming Li; et al. (Environmental Research, 2024)

Effects of exogenous application of the strigolactone GR24 on quality and flavor components during postharvest storage of celery - Mengyao Li; Xiaoyan Li; Jiageng Du; Weilong Li; Ruiyuan He; Yuanxiu Lin; Yunting Zhang; Yan Wang; Wen He; Qing Chen; Yong Zhang; Xiaorong Wang; et al. (Postharvest Biology and Technology, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Role of phosphate in microalgal-bacterial symbiosis system treating wastewater containing heavy metals - Cong-Cong Tang; Ya-Ru Hu; Min Zhang; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2024)

Spatial-temporal constraints for surface soil moisture mapping using Sentinel-1 and Sentinel-2 data over agricultural regions - ZHOU Ya'nan; WANG Binyao; ZHU Weiwei; FENG Li; HE Qisheng; ZHANG Xin; WU Tianjun; YAN Na'na (Computers and Electronics in Agriculture, 2024)

The impact of ammonia and microcystin-LR on neurobehavior and glutamate/gamma-aminobutyric acid balance in female zebrafish (Danio rerio): ROS and inflammation as key pathways - Ya He; Kang Ouyang; Hui Yang; Liangmou Wang; Xinyu Wang; Dapeng Li; Li Li (Science of The Total Environment, 2024)

An intelligent fault detection and diagnosis model for refrigeration systems with a comprehensive feature selection method - Zi-Cheng Wang; Si-Cheng Wang; Dong Li; Zhan-Wei Cao; Ya-Ling He (International Journal of Refrigeration, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Inhibiting advanced glycation end products (AGEs) of high-performance hemodialysis membranes self-assembled by gallic acid and Ti3C2Tx MXene - Qiqi Wang; Changjun Mu; Ya'nan Yu; Xia Feng; Yang He; Li Chen (Chemical Engineering Journal, 2024)

Nb2CTx MXene coating with inhibition of oxidative stress prepared by Marangoni effect for hemodialysis therapy - Yang He; Hanshu Sun; Yanjie Wang; Ya'nan Yu; Changjun Mu; Li Chen (Chemical Engineering Journal, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Environmental exposure to per- and polyfluoroalkyl substances mixture and asthma in adolescents - Yi-Fan Wang; Li Li; Xu Wang; Ya-Nan Yun; Xue-Lin Wang; En-Yang He; Ming-Kun Song; Xue-Hong Xia; Ying-Xue Zou (International Archives of Occupational and Environmental Health, 2024)

Inflammatory cell death PANoptosis is induced by the anti-cancer curaxin CBL0137 via eliciting the assembly of ZBP1-associated PANoptosome - Ya-Ping Li; Zhi-Ya Zhou; Liang Yan; Yi-Ping You; Hua-Yu Ke; Tao Yuan; Hai-Yan Yang; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Inflammation Research, 2024)

Dietary creatine promotes creatine reserves, protein deposition, and myofiber hyperplasia in muscle of juvenile largemouth bass (Micropterus salmoides) - Haodong Yu; Ya He; Mu Qin; Li Wang; Keming Rong; Xuezhen Zhang (Aquaculture, 2024)

Cold exposure, gut microbiota and health implications: A narrative review - Erkai Zhou; Ling Zhang; Li He; Ya Xiao; Kai Zhang; Bin Luo (Science of The Total Environment, 2024)

IiAGL6 participates in the regulation of stamen development and pollen formation in Isatis indigotica - Liu Yang; Xin Qiao; Hao-En He; Wei-Wei Yi; Ya-Nan Gao; Xiao-Min Tan; Hao Cheng; Xiao-Fang Hou; Ye-Ye Ma; Hong-Li Wang; Xuan Huang; Yan-Qin Ma; et al. (Plant Science, 2024)

Iron–doped bismuth oxybromides as visible−light−responsive Fenton catalysts for the degradation of atrazine in aqueous phases - Yong-Li Cai; Yu-Hang Xu; Ji-Zun Xiang; Zhi-Qiang Zhang; Qiu-Xiang He; Ya-Feng Li; Jian Lü (Journal of Environmental Sciences, 2024)

Kaili Red sour soup: Correlations in composition/microbial metabolism and flavor profile during post-fermentation - Duan Feixia; Luo Ya; Li Dafei; Zhong Dingjiang; He Guiping; Wei Zeliang; Jia Lirong (Food Chemistry, 2024)

Enzyme-immobilized nanoclay hydrogel simultaneously reduces inflammation and scar deposition to treat spinal cord injury - Tong Wu; Yajun Li; Zhiyan Wu; Ziqiang Wang; Ya Li; Ke Jian; Chaoyong He; Can Zhang; Liyang Shi; Jianwu Dai (Chemical Engineering Journal, 2024)

Natural variation of Grain size 3 allele differentially functions in regulating grain length in xian/indica and geng/japonica rice - Yong-Bin Peng; Chen-Yang Du; Ya-Nan He; Chong-Ke Zheng; Wei Sun; Jin-Jun Zhou; Li-Xia Xie; Cong-Hui Jiang; Jian-Di Xu; Fang Wang; Xian-Zhi Xie (Euphytica, 2024)

Design of an active-source seismic detection system based on illumination analysis and migration imaging experiments: considering the Zhuxi mining area as an example - Wen Li; Yong Chen; Shan-Hui Xu; Jiu-Peng Hu; Bao-Jin Liu; Yong-Peng Ouyang; Yin-Juan He; Ya-Li Tan; Xin-Sheng Hua; Jing-Jing Qin; Qian Li; Jia Jia (Applied Geophysics, 2024)

Sulfur atom-directed metal–ligand synergistic catalysis in zirconium/hafnium-oxo clusters for highly efficient amine oxidation - Sheng-Nan Sun; Qian Niu; Jiao-Min Lin; Li-Ling He; Jing-Wen Shi; Qing Huang; Jiang Liu; Ya-Qian Lan (Science Bulletin, 2024)

Self-harm and interpersonal violence due to high temperature from the global burden of disease study 2019: A 30-year assessment - Hao Zhao; Li He; Ce Liu; Xiaobing Shan; Chunyan Gui; Ling Zhang; Yunhui Yu; Ya Xiao; Jia Xue; Kai Zhang; Bin Luo (Environmental Research, 2024)

New insights into endocrine reproductive toxicity of Microcystis aeruginosa combined with ammonia exposure in zebrafish - Kang Ou-Yang; Qian Zhang; Liangmou Wang; Hui Yang; Ya He; Dapeng Li; Li Li (Environmental Pollution, 2024)

A novel R2R3-MYB transcription factor PbMYB1L of Pyrus bretschneideri regulates cold tolerance and anthocyanin accumulation - Xuan Zhou; Diya Lei; Wantian Yao; Shangyun Li; Haiyan Wang; Jiayu Lu; Yunting Zhang; Yuanxiu Lin; Yan Wang; Wen He; Mengyao Li; Qing Chen; et al. (Plant Cell Reports, 2024)

Peroxisome Proliferator-Activated Receptor-γ Coactivator-1α in the Spotlight with Multiple Sclerosis - Ya-Na Yang; Mao-Qing Zhang; Feng-Lin Yu; Bing Han; Ming-Yue Bao; Yan He; Xing Li; Yuan Zhang (Neuroscience Bulletin, 2024)

Expansion of YALIcloneHR toolkit for Yarrowia lipolytica combined with Golden Gate and CRISPR technology - Qi Shen; Fang Yan; Ya-Wen Li; Jian Wang; Jia Ji; Wen-Xin Yan; Dan-Chen He; Ping Song; Tian-Qiong Shi (Biotechnology Letters, 2024)

Comparison of muscle structure and transcriptome analysis reveals the mechanism of growth variation in Yangtze sturgeon (Acipenser dabryanus) - Qingzhi Li; Jun Wang; Yeyu Chen; Xiaoyun Wu; Ya Liu; Jiansheng Lai; Mingjiang Song; Feiyang Li; Pengcheng Li; Bin He; Bin Wang; Tao Yan; et al. (Aquaculture, 2024)

Adaptive evolution in asymptomatic host confers MDR Salmonella with enhanced environmental persistence and virulence - Bing He; Ting-ting Zhu; Yin Liang; Hai-jing Wei; Zi-lei Huang; Li-jie Liang; Jia-hao Zhong; Yang Luo; Xin-lei Lian; Dong-hao Zhao; Xiao-ping Liao; Ya-hong Liu; et al. (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Multiomics analyses of two Leonurus species illuminate leonurine biosynthesis and its evolution - Peng Li; Meng-Xiao Yan; Pan Liu; Dan-Jie Yang; Ze-Kun He; Yun Gao; Yan Jiang; Yu Kong; Xin Zhong; Sheng Wu; Jun Yang; Hong-Xia Wang; et al. (Molecular Plant, 2024)

Chromium contents, distribution and bioaccessibility in cultivated mushrooms from market: Health implications for human consumption - Wen-Jie Dong; Si-Xue He; Xing-Yue Li; Jing-Yu Zeng; Meng-Ya Li; Dong-Xing Guan; Lena Q. Ma (Journal of Hazardous Materials, 2024)

Multi-omics analysis reveals the toxic mechanism of ammonia-enhanced Microcystis aeruginosa exposure causing liver fat deposition and muscle nutrient loss in zebrafish - Kang Ou-Yang; Yu Kuang; Hui Yang; Ya He; Liangmou Wang; Xinyu Wang; Dapeng Li; Li Li (Journal of Hazardous Materials, 2024)

Instability in a carbon pool driven by multiple dissolved organic matter sources in a eutrophic lake basin: Potential factors for increased greenhouse gas emissions - Jie Ma; Muchun Zhou; Yu Peng; Ya Tuo; Chuanqiao Zhou; Kexin Liu; Yilin Huang; Fei He; Qiuying Lai; Zhihui Zhang; Tsuyoshi Kinouchi; Shuyin Li; et al. (Journal of Environmental Management, 2024)

The benefit of omeprazole exposure on all-cause mortality and length of ICU/hospital stay might vary with age in critically ill pediatric patients: A cohort study - Fang-Fang Jiang; Yu Guo; Zheng Zhang; Sun-Jun Yin; Yu-Xin Fan; Yan-Hua Huang; Ya-Jia Li; Li-Rong Chen; Kai Qian; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Uptake, translocation, accumulation, and metabolism of fluroxypyr-meptyl and oxidative stress induction in rice seedling - Zhao Jie Chen; Hao Wen Wang; Si Ying Li; Yong Heng Zhang; Ya Nan Qu; Zhi Hai He; Xue Sheng Li; Xiao Liang Liu (Environmental Science and Pollution Research, 2023)

Porosity prediction in tight sandstone reservoirs based on a one–dimensional convolutional neural network–gated recurrent unit model - Su-Zhen Shi; Gui-Fei Shi; Jin-Bo Pei; Li-Li; Kang Zhao; Ya-Zhou He (Applied Geophysics, 2023)

Combined effects of microcystin-LR and rice straw-derived biochar on the hepatic antioxidant capacity of zebrafish: Insights from LC-MS/MS-based metabolomics analysis - Wang Lin; Kang Ouyang; Ya He; Hui Yang; Yu Kuang; Dapeng Li; Li Li (Science of The Total Environment, 2023)

Endophytic Bacillus sp. R1 and Its Roles in Assisting Phytoremediation and Alleviating the Toxicity of Aluminum Combined Phenanthrene Contaminations in Brassica napus - Li-rong Fang; Xue-cheng Yang; Chun-ya Wu; Kai Sun; Mallavarapu Megharaj; Wei He (Current Microbiology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

TBtools-II: A “one for all, all for one” bioinformatics platform for biological big-data mining - Chengjie Chen; Ya Wu; Jiawei Li; Xiao Wang; Zaohai Zeng; Jing Xu; Yuanlong Liu; Junting Feng; Hao Chen; Yehua He; Rui Xia (Molecular Plant, 2023)

Bioinspired yeast-based β-glucan system for oral drug delivery - Ya Wu; Pengyun Li; Zongzhe Jiang; Xiaolei Sun; Huqiang He; Pijun Yan; Yong Xu; Yong Liu (Carbohydrate Polymers, 2023)

Ångstrom-scale silver particles ameliorate collagen-induced and K/BxN-transfer arthritis in mice via the suppression of inflammation and osteoclastogenesis - Ze-Hui He; Jing-Tao Zou; Xia Chen; Jiang-Shan Gong; Ya Chen; Ling Jin; Yi-Wei Liu; Shan-Shan Rao; Hao Yin; Yi-Juan Tan; Zun Wang; Wei Du; et al. (Inflammation Research, 2023)

Oxygen Vacancies of Mn/CeOx-H induced non-radical activation of peroxymonosulfate through electron mediation for bisphenol A degradation - Junyong He; Ya Yang; Peidong Hong; Yulian Li; Chao Xie; Zijian Wu; Minqiang Li; Lingtao Kong (Journal of Environmental Chemical Engineering, 2023)

Customizing CoSe2/Ti3C2Tn MXene hybrid inks toward high-energy-density 3D-printed K-ion hybrid capacitors - Wenfeng Liu; Yuyang Yi; Zeyu He; Tao Han; Jingyu Sun; Ji Zhou; Ya-yun Li (Chemical Engineering Journal, 2023)

Conditioned medium of human menstrual blood-derived endometrial stem cells protects against cell inflammation and apoptosis of Npc1KO N2a cells - Minlin Yang; Yanchun Zhao; Xiaoying Li; Han Li; Fangfang Cheng; Yanli Liu; Zisen Jia; Ya’nan He; Juntang Lin; Lihong Guan (Metabolic Brain Disease, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Mechanisms of feeding cessation in Helicoverpa armigera larvae exposed to Bacillus thuringiensis Cry1Ac toxin - Kaixia Li; Shan Yu; Yihua Yang; Ya-Zhou He; Yidong Wu (Pesticide Biochemistry and Physiology, 2023)

Rice Straw Biochar is More Beneficial to Soil Organic Carbon Accumulation and Stabilization than Rice Straw and Rice Straw Ash - Mengru He; Ya Jiang; Yuhang Han; Wenhao Zhu; Da Meng; Cuilan Li; Hongguang Cai; Jinjing Zhang (Journal of Soil Science and Plant Nutrition, 2023)

Microcystin-LR immersion caused sequential endocrine disruption and growth inhibition in zebrafish (Danio rerio) from fertilization to sexual differentiation completion - Ya He; Jie Hou; Yuming Qiu; Kang Ouyang; Dapeng Li; Li Li (Toxicology, 2023)

Lateral performance of mortise-tenon jointed frames in multi-story traditional heavy timber structures: Mechanism and quantification - Ya-Jie Wu; He-Shou Lin; Lei Wang; Qi-Fang Xie; Li-Peng Zhang (Engineering Structures, 2023)

Two new isoflavones from the barks of Dalbergia hancei Benth - Xiao-Mei Li; Nao Pang; Ya-Feng Wang; Rui-Jie He; Li Ge; Bing-Yuan Yang; Ke-Di Yang; Yong-Lin Huang (Natural Product Research, 2023)

Aggregation enhanced FRET: A simple but efficient strategy for the ratiometric detection of uranyl ion - Dan Wang; Li-Jie Zhang; Ming-Hui Liu; Fang-Fang Du; Ze-Ya Shen; Longwei He; Li-Li Wang (Journal of Hazardous Materials, 2023)

Pulsed counterclockwise rotation of the southwestern Sichuan Basin in response to the India-Asia convergence during 128-42 Ma - Qi Shen; Chun-Sheng Jin; Wen-Tian Liang; Chuan-Zhi Li; Hui-Hui Yang; Ya-Zhou Ran; Xuan He; Guan-Zuo Wu; Kai Jiang; Jian-Gang Li; Peng Han; Si-Hua Yuan (Earth and Planetary Science Letters, 2023)

Coaxial electrospun nanofibrous substrates with tunable wettability for constructing cucurbit[n]uril-embedded organic solvent nanofiltration membranes - Qian Wang; Qin-Yuan He; Liu-Lin Zhao; Yue Wang; Rong Fang; Cong Luo; Wei-Tong Lu; Hong-Ya Jiang; Shi-Peng Sun; Xue-Li Cao (Chemical Engineering Journal, 2023)

4-OI ameliorates bleomycin-induced pulmonary fibrosis by activating Nrf2 and suppressing macrophage-mediated epithelial-mesenchymal transition - Ya-xian Wu; Ya-ru Zhang; Feng-juan Jiang; Shuai He; Yan-li Zhang; Dan Chen; Ying Tong; Yun-juan Nie; Qing-feng Pang (Inflammation Research, 2023)

Click-crosslinked in-situ hydrogel improves the therapeutic effect in wound infections through antibacterial, antioxidant and anti-inflammatory activities - Xiong-Xin Lei; Chen-Yu Zou; Juan-Juan Hu; Yan-Lin Jiang; Xiu-Zhen Zhang; Long-Mei Zhao; Tao He; Qing-Yi Zhang; Ya-Xing Li; Jesse Li-Ling; Hui-Qi Xie (Chemical Engineering Journal, 2023)

Methimazole and sodium perchlorate exert anti-thyroidal effects in the T3-induced Xenopus laevis metamorphosis assay: A rapid assay for screening thyroid disrupting chemicals - Wei Zhou; Zhan-Fen Qin; Yuan-Yuan Li; Jin-Bo Li; Ya-li Shi; Miao-xin Dong; Xiang Li; Yong-Jun Zhang; Yi-De He (Aquatic Toxicology, 2023)

Identification of a new benzophenanthridine alkaloid from Eomecon chionantha induced necroptosis in breast cancer cells - Peng Yang; Ya-ting Cheng; Xin Huang; Bin Huang; Li Yi; Hai-lang He; Yang Xie (Natural Product Research, 2023)

Nitrogen−doped−CQDs/schwertmannites as visible−light−responsive Fenton catalysts for the degradation of chlortetracycline and related cytotoxicity - Yu-Hang Xu; Xiang-Ji Liu; Ji-Zun Xiang; Zhi-Qiang Zhang; Xing-Xing Qiao; Ya-Feng Li; Qiu-Xiang He; Jian Lü (Journal of Cleaner Production, 2023)

Boosting the photocatalytic hydrogen evolution and NO removal via synergistic effects of in-situ Pt NPs formation and titanium integration in Zr-Porphyrin MOFs - Ruolan Li; Zongqian Wu; Ya Chen; Xingyan Liu; Weiwei Guo; Yumin Huang; Min Fu; Youzhou He (Fuel, 2023)

The protective role of vitamin C on intestinal damage induced by high-dose glycinin in juvenile Rhynchocypris lagowskii Dybowski - Rui Zhu; Zongyu Liu; Minghui Lu; Xueqin Wu; Xueyuan Zhao; Hong-He Wang; Ya-Nan Quan; Li-Fang Wu (Fish & Shellfish Immunology, 2023)

Potential of crop straw incorporation for replacing chemical fertilizer and reducing nutrient loss in Sichuan Province, China - Ying Wang; Bang-qiang Liang; Hui Bao; Qian Chen; Ya-lei Cao; Yan-qing He; Liang-zhong Li (Environmental Pollution, 2023)

Neogene subduction initiation models in the western Pacific and analysis of subduction zone parameters - Min Li; Song Huang; Tianyao Hao; Miao Dong; Ya Xu; Jian Zhang; Qingyu He; Gui Fang (Science China Earth Sciences, 2023)

TCR repertoire landscape reveals macrophage-mediated clone deletion in endotoxin tolerance - Juanjuan Zhao; Li Jia; YiJing Tao; Xu Zhao; Jing Yang; Yanxin Lu; Yaping Yan; Ling Mao; Lin Hu; Jia Lu; MengMeng Guo; Chao Chen; et al. (Inflammation Research, 2023)
Background Endotoxin tolerance (ET) is a protective mechanism in the process of sepsis, septic shock, and their sequelae including uncontrolled inflammation. Accumulating evidence has shown that peripheral T cells contribute to the induction of ET. However, what and how T-cell development contributes to ET inductions remain unclear. Methods Mice were intraperitoneally injected with LPS at a concentration of 5 mg/kg to establish an LPS tolerance model and were divided into two groups: a group examined 72 h after LPS injection (72-h group) and a group examined 8 days after LPS injection (8-day group). Injection of PBS was used as a control. We performed high-throughput sequencing to analyze the characteristics and changes of CD4 + SP TCR β CDR3 repertoires with respect to V direct to J rearrangement during the ET induction. Moreover, the proportion and proliferation, as well as surface molecules such as CD80 and CD86, of F4/80 + macrophages were analyzed using FCM. Furthermore, ACT assay was designed and administered by the tail vein into murine LPS-induced mouse model to evaluate the role of F4/80 + macrophages on the development of CD4 + SP thymocytes in ET condition. Results We found that the frequency and characteristics of the TCR β chain CDR3 changed obviously under condition of ET, indicating the occurrence of TCR rearrangement and thymocyte diversification. Moreover, the absolute numbers of F4/80 + macrophages, but not other APCs, were increased in thymic medulla at 72-h group, accompanied by the elevated function-related molecules of F4/80 + macrophages. Furthermore, adoptively transferred OVA 332-339 peptide-loaded macrophages into Rag-1 −/− mice induced the clone deletion of OVA-specific CD4 + SP, thereby ameliorating the pathology in lung tissue in LPS challenge. Conclusions These data reveal that the frequency and characteristics of the TCR β chain CDR3 undergo dynamic programming under conditions of LPS tolerance. Furthermore, the peripheral macrophages may be a key factor which carry peripheral antigen to thymic medulla and affect the negative selection of T-cell population, thereby contributing to the formation of ET. These results suggest that the clone selection in thymus in ET may confer protection against microbial sepsis.

Establishment of an efficient method for kiwifruit in vitro micrografting - Wantian Yao; Lingling Kong; Diya Lei; Bing Zhao; Honglan Tang; Xuan Zhou; Yuanxiu Lin; Yunting Zhang; Yan Wang; Wen He; Mengyao Li; Qing Chen; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Correction to: Ketone Body Rescued Seizure Behavior of LRP1 Deficiency in Drosophila by Modulating Glutamate Transport - Jin-Ming Zhang; Ming-Jie Chen; Jiong-Hui He; Ya-Ping Li; Zhi-Cai Li; Zi-Jing Ye; Yong-Hui Bao; Bing-Jun Huang; Wen-Jie Zhang; Ping Kwan; Yu-Ling Mao; Jing-da Qiao (Journal of Molecular Neuroscience, 2023)

Scaling-up and proteomic analysis reveals photosynthetic and metabolic insights toward prolonged H2 photoproduction in Chlamydomonas hpm91 mutant lacking proton gradient regulation 5 (PGR5) - Peng Liu; De-Min Ye; Mei Chen; Jin Zhang; Xia-He Huang; Li-Li Shen; Ke-Ke Xia; Xiao-Jing Xu; Yong-Chao Xu; Ya-Long Guo; Ying-Chun Wang; Fang Huang (Photosynthesis Research, 2022)
Clean and sustainable H 2 production is crucial to a carbon–neutral world. H 2 generation by Chlamydomonas reinhardtii is an attractive approach for solar-H 2 from H 2 O. However, it is currently not large-scalable because of lacking desirable strains with both optimal H 2 productivity and sufficient knowledge of underlying molecular mechanism. We hereby carried out extensive and in-depth investigations of H 2 photoproduction of hpm91 mutant lacking PGR5 (Proton Gradient Regulation 5) toward its up-scaling and fundamental mechanism issues. We show that hpm91 is at least 100-fold scalable (up to 10 L) with continuous H 2 collection of 7287 ml H 2 /10L-HPBR in averagely 26 days under sulfur deprivation. Also, we show that hpm91 is robust and active during sustained H 2 photoproduction, most likely due to decreased intracellular ROS relative to wild type. Moreover, we obtained quantitative proteomic profiles of wild type and hpm91 at four representing time points of H 2 evolution, leading to 2229 and 1350 differentially expressed proteins, respectively. Compared to wild type, major proteome alterations of hpm91 include not only core subunits of photosystems and those related to anti-oxidative responses but also essential proteins in photosynthetic antenna, C/N metabolic balance, and sulfur assimilation toward both cysteine biosynthesis and sulfation of metabolites during sulfur-deprived H 2 production. These results reveal not only new insights of cellular and molecular basis of enhanced H 2 production in hpm91 but also provide additional candidate gene targets and modules for further genetic modifications and/or in artificial photosynthesis mimics toward basic and applied research aiming at advancing solar-H 2 technology.

Low-Level Environmental Per- and Polyfluoroalkyl Substances and Preterm Birth: A Nested Case–Control Study Among a Uyghur Population in Northwestern China - Bo-Yi Yang; Jianhua Wu; Xilong Niu; Chuanjiang He; Michael S. Bloom; Maihefuzaimu Abudoukade; Mairiyemu Abulizi; Aimin Xu; Beibei Li; Li Li; Xuemei Zhong; Qi-Zhen Wu; et al. (Exposure and Health, 2022)

Isolation, identification, and quantification of triterpene saponins in the fresh fruits of Panax notoginseng - Zheng-yi Qu; He-cheng Wang; Yin-ping Jin; Ya-li Li; Ying-ping Wang (Natural Product Research, 2022)

Three new compounds from the leaves of Castanopsis tibetana Hance - Ya-Feng Wang; Rui-Jie He; Dian-Peng Li; Yong-Lin Huang (Natural Product Research, 2022)

Siccirubricoccus soli sp. nov., a novel bacterial species isolated from Jiaozi Mountain soil - Guo-Xing Zhu; Ya-Jie Wu; Yan-Ru Cao; Bing-Jun Fan; Yu Jiao; Xiu-Li Hou; Zi-Chao Liu; Yue Zhang; Jiang-Bo He; Lian-Ming Liang (Antonie van Leeuwenhoek, 2022)

Evaluating the Response of a Tunnel Subjected to Strike-Slip Fault Rupture in Conjunction with Model Test and Hybrid Discrete–Continuous Numerical Modeling - Cui Zhen; Li Jian-he; Fu Xing-wei; Sheng Qian; Zhou Guang-xin; Ma Ya-li-na; Wang Tian-qiang (Rock Mechanics and Rock Engineering, 2022)

Ketone Body Rescued Seizure Behavior of LRP1 Deficiency in Drosophila by Modulating Glutamate Transport - Jin-Ming Zhang; Ming-Jie Chen; Jiong-Hui He; Ya-Ping Li; Zhi-Cai Li; Zi-Jing Ye; Yong-Hui Bao; Bing-Jun Huang; Wen-Jie Zhang; Ping Kwan; Yu-Ling Mao; Jing-da Qiao (Journal of Molecular Neuroscience, 2022)

Inhibition of visfatin alleviates sepsis-induced intestinal damage by inhibiting Hippo signaling pathway - Zhong-Shen Kuang; Yu-Xin Leng; Ning Yang; Zheng-Qian Li; Ya-Nan Zong; Deng-Yang Han; Yue Li; Jin-Dan He; Xing-Ning Mi; Zhu-Kai Cong; Xi Zhu; Chang-Yi Wu; et al. (Inflammation Research, 2022)
Background The aim of this study is to investigate role of Visfatin, one of the pro-inflammatory adipokines, in sepsis-induced intestinal injury and to clarify the potential mechanism. Methods C57BL/6 mice underwent cecal ligation and puncture (CLP) surgery to establish sepsis model in vivo. Intestinal epithelial cells were stimulated with LPS to mimic sepsis-induced intestinal injury in vitro. FK866 (the inhibitor of Visfatin) with or without XMU-MP-1 (the inhibitor of Hippo signaling) was applied for treatment. The expression levels of Visfatin, NF-κB and Hippo signaling pathways-related proteins were detected by western blot or immunohistochemistry. The intestinal cell apoptosis and intestinal injury were investigated by TUNEL staining and H&E staining, respectively. ELISA was used to determine the production of inflammatory cytokines. Results The expression of Visfatin increased in CLP mice. FK866 reduced intestinal pathological injury, inflammatory cytokines production, and intestinal cell apoptosis in sepsis mice. Meanwhile, FK866 affected NF-κB and Hippo signaling pathways. Additionally, the effects of FK866 on inflammatory response, apoptosis, Hippo signaling and NF-κB signaling were partly abolished by XMU-MP-1, the inhibitor of Hippo signaling. In vitro experiments also revealed that FK866 exhibited a protective role against LPS-induced inflammatory response and apoptosis in intestinal cells, as well as regulating NF-κB and Hippo signaling, whereas addition of XMU-MP-1 weakened the protective effects of FK866. Conclusion In short, this study demonstrated that inhibition of Visfatin might alleviate sepsis-induced intestinal injury through Hippo signaling pathway, supporting a further research on Visfatin as a therapeutic target.

Feed types affect the growth, nutrient utilization, digestive capabilities, and endocrine functions of Megalobrama amblycephala: a comparative study between pelleted and extruded feed - Chao-Fan He; Xiang-Fei Li; Guang-Zhen Jiang; Ling Zhang; Miao Sun; Ya-Ping Ge; Wei-Liang Chen; Wen-Bin Liu (Fish Physiology and Biochemistry, 2022)

Exposure characteristics of phthalate metabolites among the Zunyi cohort of pregnant women in Southwest China - Juan Liao; Derong Fang; Yijun Liu; Shimin Xiong; Xia Wang; Yingkuan Tian; Haonan Zhang; Songlin An; Caidie He; Wei Chen; Xiang Liu; Nian Wu; et al. (Environmental Science and Pollution Research, 2022)

Stable Isotopes Reveal Water Vapor Sources of Precipitation over the Jiaolai Plain, Shandong Peninsula, China - Ying Wang; Bu-li Cui; Dong-sheng Li; Ya-xuan Wang; Wan-xin Yu; He-hua Zong (Asia-Pacific Journal of Atmospheric Sciences, 2022)

Novel bioavailability-based risk assessment of Cd in earthworms and leeches utilizing in vitro digestion/Caco-2 and MDCK cells - Tian-tian Zuo; Fei-ya Luo; Huai-zhen He; Hong-yu Jin; Lei Sun; Shu-xia Xing; Bo Li; Fei Gao; Shuang-cheng Ma; Lang-chong He (Environmental Science and Pollution Research, 2022)

Mitogenome of Knodus borki (Cypriniformes: Characidae): genomic characterization and phylogenetic analysis - Cheng-He Sun; Ya-Nan Zhang; Xiao-Shu Zeng; Da-Wei Liu; Qi Huang; Xiao-Li Zhang; Qun Zhang (Molecular Biology Reports, 2022)

The association between short-term ambient air pollution and acne vulgaris outpatient visits: a hospital-based time-series analysis in Xi’an - Xiang Li; Yi Cao; Shu-Jie An; Ying Xiang; He-Xiang Huang; Bin Xu; Yao Zhang; Ya-Fei Li; Yuan-Gang Lu; Tong-Jian Cai (Environmental Science and Pollution Research, 2022)

Evaluation of suitable qRT-PCR normalization genes for various citrus rootstocks - Wen He; Rui Xie; Huan Li; Yan Wang; Qing Chen; Yuanxiu Lin; Yunting Zhang; Ya Luo; Yong Zhang; Haoru Tang; Xiaorong Wang (Plant Biotechnology Reports, 2022)

Air pollution increased risk of reproductive system diseases: a 5-year outcome analysis of different pollutants in different seasons, ages, and genders - Ya Li; Juan Du; Shanshan Lin; Huihui He; Rui Jia; Weihong Liu (Environmental Science and Pollution Research, 2022)

Assessment of probiotic adhesion and inhibitory effect on Escherichia coli and Salmonella adhesion - Ya Wang; Dan Jia; Jia-hui Wang; He-hai Li; Jun-long Liu; Ai-hong Liu; Jin-ming Wang; Gui-quan Guan; Jian-xun Luo; Hong Yin; You-quan Li (Archives of Microbiology, 2021)

The chemical profile and biological activity of different extracts of Sapindus mukorossi Gaertn. against Cutibacterium acnes - Min-Ping Wei; Jin-Dan Qiu; Lu Li; Yun-Fei Xie; Ya-Hui Guo; Hang Yu; Yu-Liang Cheng; He Qian; Wei-Rong Yao (Natural Product Research, 2021)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

BDS-3 SAR service and initial performance - Gang Li; Shuren Guo; Zehua He; Ya Gao; Wenxuan Li (GPS Solutions, 2021)

Interaction of magnolia bark extracts with Staphylococcus aureus DNA and evaluation of the stability of their antibacterial activities - Shu-Mei Cui; Hai-yun Liang; Ting Li; Ke-Ke He; Yu-Mei Zheng; Meng Tang; Chong-rong Ke; Li-Ya Song (Archives of Microbiology, 2021)

Design, synthesis, and antidepressant/anticonvulsant activities of 3H-benzo[f]chromen chalcone derivatives - Qiu-Wan Tan; Li-Ya He; Zhi-Wen He; Wei-Hua Liu; Shan-Shan Zhang; Lin Lin; Hong-Li Yang; Li-Ping Guan (Medicinal Chemistry Research, 2021)

Allotransplantation of adult spinal cord tissues after complete transected spinal cord injury: Long-term survival and functional recovery in canines - He Shen; Shuyu Wu; Xi Chen; Bai Xu; Dezun Ma; Yannan Zhao; Yan Zhuang; Bing Chen; Xianglin Hou; Jiayin Li; Yudong Cao; Xianyong Fu; et al. (Science China Life Sciences, 2020)

Greater promotion of DNRA rates and nrfA gene transcriptional activity by straw incorporation in alkaline than in acidic paddy soils - Ren Bai; Yun-Ting Fang; Liu-Ying Mo; Ju-Pei Shen; Lin-Lin Song; Ya-Qi Wang; Li-Mei Zhang; Ji-Zheng He (Soil Ecology Letters, 2020)

Influence of complex topography on magnetotelluric-observed data using three-dimensional numerical simulation: A case from Guangxi area, China - Xiong Bin; Luo Tian-Ya; Chen Long-Wei; Dai Shi-Kun; Xu Zhi-Feng; Li Chang-Wei; Ding Yan-Li; Wang Hong-Hua; Li Jing-He (Applied Geophysics, 2020)

Highly sensitive serological approaches for Pepino mosaic virus detection - Wan-qin He; Jia-yu Wu; Yi-yi Ren; Xue-ping Zhou; Song-bai Zhang; Ya-juan Qian; Fang-fang Li; Jian-xiang Wu (Journal of Zhejiang University-SCIENCE B, 2020)

Retrospective analysis of HIV-1 drug resistance mutations in Suzhou, China from 2009 to 2014 - Yanhui Song; Jingping Hu; Jun He; Chunsheng Dong; Ying Yuan; Yuan Li; Ronghua Li; Xuerong Ya (Virus Genes, 2020)

Molecular epidemiology of enteroviruses associated with severe hand, foot and mouth disease in Shenzhen, China, 2014-2018 - Long Chen; Shao-Jian Xu; Xiang-Jie Yao; Hong Yang; Hai-Long Zhang; Jun Meng; Han-Ri Zeng; Xu-He Huang; Ren-Li Zhang; Ya-Qing He (Archives of Virology, 2020)

High throughput solid-phase screening of bacteria with cyclic amino alcohol deamination activity for enantioselective synthesis of chiral cyclic β-amino alcohols - Ya-Wen Chang; Jian-Dong Zhang; Xiao-Xiao Yang; Jing Li; Li-Li Gao; Shuang-Ping Huang; Xing-Mei Guo; Cao-Feng Zhang; Hong-Hong Chang; Jian-He Xu (Biotechnology Letters, 2020)

Naphthalene exerts non-target effects on the abundance of active fungi by stimulating basidiomycete abundance - Li-ying Lan; Li Zhang; Ya Shen; Jian Zhang; Wan-qin Yang; Zhen-feng Xu; Yang Liu; Shu-qin He; Wei Zhou; Han Li; Li-xia Wang; Si-ning Liu; et al. (Journal of Mountain Science, 2020)

Antibacterial Effects of Schisandra chinensis Extract on Escherichia coli and its Applications in Cosmetic - S. Mei Cui; T. Li; Q. Wang; K. Ke He; Y. Mei Zheng; H. Yun Liang; L. Ya Song (Current Microbiology, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Application of metagenomic next-generation sequencing for bronchoalveolar lavage diagnostics in critically ill patients - Ying Li; Bing Sun; Xiao Tang; Ya-lan Liu; Hang-yong He; Xu-yan Li; Rui Wang; Fei Guo; Zhao-hui Tong (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Genetic analysis and fine mapping of phosphorus efficiency locus 1 (PE1) in soybean - Yongqing Yang; Ya Tong; Xinxin Li; Ying He; Ruineng Xu; Dong Liu; Qing Yang; Huiyong Lv; Hong Liao (Theoretical and Applied Genetics, 2019)

Association of the Polymorphism of rs1799822 on Carnitine Palmitoyltransferase II Gene with Severe Enterovirus 71 Encephalitis in Chinese Children - Ya Guo; Yu Zhang; Peipei Liu; Fei Li; Dandan Xin; Hongfang He; Yedan Liu; Chengqing Yang; Zongbo Chen (Journal of Molecular Neuroscience, 2019)

Influence of Different Propulsion Speeds on the Characteristics of Mine Pressure in the Fully Mechanized Caving Face During Rotary Stage - Liang Li; Xue He; Yong-qiang Chen; Ya-chun Li; Chen-hao Shi; Yu-ping Zhu (Geotechnical and Geological Engineering, 2019)

DNA methylation and mRNA expression of COL6A3 in antler mesenchyme of female and male reindeer - Jian-Cheng Zhai; Ruo-Bing Han; Sheng-Nan Wang; Qiang-Hui Wang; Yan-Ling Xia; Wei-Shi Liu; Ya-Jie Yin; He-Ping Li (Genes & Genomics, 2019)

Potential hypoglycemic effect of acetophenones from the root bark of Cynanchum wilfordii - Hao-Wen Jiang; Shan-Shan Gu; Lei Cao; Sheng-Shi Jiang; Jing Lin; Yan Chen; Ling Wang; He Jiao; Jing-Ya Li; Wei-Min Zhao; Jin-Long Li (Natural Product Research, 2019)

Methane emissions responding to Azolla inoculation combined with midseason aeration and N fertilization in a double-rice cropping system - Ya-Dong Yang; He-Shui Xu; Deng-Yun Li; Jing-Na Liu; Jiang-Wen Nie; Zhao-Hai Zeng (Environmental Science and Pollution Research, 2019)

Molecular surveillance of coxsackievirus A16 reveals the emergence of a new clade in mainland China - Long Chen; Xiang-Jie Yao; Shao-Jian Xu; Hong Yang; Chun-Li Wu; Jing Lu; Wen-Bo Xu; Hai-Long Zhang; Jun Meng; Yong Zhang; Ya-Qing He; Ren-Li Zhang (Archives of Virology, 2019)

Anti-Hypertensive Action of Fenofibrate via UCP2 Upregulation Mediated by PPAR Activation in Baroreflex Afferent Pathway - Jian Guan; Miao Zhao; Chao He; Xue Li; Ying Li; Jie Sun; Wei Wang; Ya-Li Cui; Qing Zhang; Bai-Yan Li; Guo-Fen Qiao (Neuroscience Bulletin, 2019)

Frond transformation system mediated by Agrobacterium tumefaciens for Lemna minor - Gui-Li Yang; Yang Fang; Ya-Liang Xu; Li Tan; Qi Li; Yang Liu; Fan Lai; Yan-Ling Jin; An-Ping Du; Kai-Ze He; Xin-Rong Ma; Hai Zhao (Plant Molecular Biology, 2018)

Soil physicochemical properties and vegetation structure along an elevation gradient and implications for the response of alpine plant development to climate change on the northern slopes of the Qilian Mountains - Yong-sheng Yang; Li Zhang; Hong-qin Li; Hui-dan He; Ya-xi Wei; Jin Luo; Guang-ru Zhang; Yu-ru Huang; Ying-nian Li; Hua-kun Zhou (Journal of Mountain Science, 2018)

Impact of IL-10-1082A/G gene polymorphism on the severity of EV71 infection in Chinese children - Qiubo Li; Hongfang He; Ya Guo; Yu Zhang; Peipei Liu; Yedan Liu; Chengqing Yang; Jie Song; Na Zhang; Zongbo Chen (Archives of Virology, 2018)

First report of pileus rot disease on cultivated Morchella importuna caused by Diploöspora longispora in China - Peixin He; Congcong Li; Yingli Cai; Ya Zhang; Yinbing Bian; Wei Liu (Journal of General Plant Pathology, 2018)

Inhibitory effects of Dioscin on atherosclerosis and foam cell formation in hyperlipidemia rats - Ping Wang; Li-ya He; Guo-dong Shen; Rui-lin Li; Jun-li Yang (Inflammopharmacology, 2017)

Administration of fentanyl via a slow intravenous fluid line compared with rapid bolus alleviates fentanyl-induced cough during general anesthesia induction - Min-qiang Liu; Feng-xian Li; Ya-kun Han; Jun-yong He; Hao-wen Shi; Li Liu; Ren-liang He (Journal of Zhejiang University-SCIENCE B, 2017)

MiR-181b Antagonizes Atherosclerotic Plaque Vulnerability Through Modulating Macrophage Polarization by Directly Targeting Notch1 - Tian-Hui An; Quan-Wei He; Yuan-Peng Xia; Sheng-Cai Chen; Suraj Baral; Ling Mao; Hui-Juan Jin; Ya-Nan Li; Meng-Die Wang; Jian-Guo Chen; Ling-Qiang Zhu; Bo Hu (Molecular Neurobiology, 2017)

Assessment of arsenic trioxide toxicity on cock muscular tissue: alterations of oxidative damage parameters, inflammatory cytokines and heat shock proteins - Si-wen Li; Ying Guo; Ying He; Xiao Sun; Hong-jing Zhao; Yu Wang; Ya-jun Wang; Ming-wei Xing (Ecotoxicology, 2017)

Novel adefovir mono L-amino acid ester, mono bile acid ester derivatives: Design, synthesis, biological evaluation, and molecular docking study - Ya Chen; Wen Zheng Zhang; Jing Li; Tao Xiao; Jiang Xia Liu; Min Luo; Hang Su; Xiao-Zhong Fu; Ting Liu; Yong-Xi Dong; Yong-Long Zhao; Bin He; et al. (Medicinal Chemistry Research, 2017)

Adjuvant effects mediated by the carbohydrate recognition domain of Agrocybe aegerita lectin interacting with avian influenza H9N2 viral surface glycosylated proteins - Li-bao Ma; Bao-yang Xu; Min Huang; Lv-hui Sun; Qing Yang; Yi-jie Chen; Ya-lin Yin; Qi-gai He; Hui Sun (Journal of Zhejiang University-SCIENCE B, 2017)

Association of Toll-like receptor 3 gene polymorphism with the severity of enterovirus 71 infection in Chinese children - Hongfang He; Shihai Liu; Pei-pei Liu; Qiu-bo Li; Yu-xia Tan; Ya Guo; Fei Li; Yuan-yuan Wang; Ye-dan Liu; Cheng-qing Yang; Zong-bo Chen (Archives of Virology, 2017)

Research and application of spectral inversion technique in frequency domain to improve resolution of converted PS-wave - Hua Zhang; Zhen-Hua He; Ya-Lin Li; Rui Li; Guamg-Ming He; Zhong Li (Applied Geophysics, 2017)

Establishment of mouse leukemia cell lines expressing human CD4/CCR5 using lentiviral vectors - Ya-jing Li; Fu-yan ZhuGe; Chang-chun Zeng; Jin-yang He; Ning Tan; Juan Liang (Virus Genes, 2017)

Laboratory study on cement admixed marine silt bricks - Yu-Feng Gao; Li-Ya Wang; Yu-Kuai Wan; Bing Li; Jia He (Marine Georesources & Geotechnology, 2017)

Glucocorticoids Prevent Enterovirus 71 Capsid Protein VP1 Induced Calreticulin Surface Exposure by Alleviating Neuronal ER Stress - Dan-Dan Hu; Jian-Ning Mai; Li-Ya He; Pei-Qing Li; Wen-Xiong Chen; Jian-Jiang Yan; Wei-Dong Zhu; Li Deng; Dan Wei; Di-Hui Liu; Si-Da Yang; Zhi-Bin Yao (Neurotoxicity Research, 2017)

A bifunctional type III polyketide synthase from raspberry (Rubus idaeus L.) with both chalcone synthase and benzalacetone synthase activity - Hui-Li Guo; Ya-Dong Yang; Ya-Di Ma; Wen-Bin Liu; Jing Feng; Zai-Qi Luo; He-Shu Lu; Chun-Mei Liu; Ming-Feng Yang; You-Nian Wang; Lan-Qing Ma (Journal of Plant Biochemistry and Biotechnology, 2017)

Hepatic expression of transcription factors affecting developmental regulation of UGT1A1 in the Han Chinese population - Ya-li Nie; Hang He; Jiang-feng Li; Xiang-guang Meng; Liang Yan; Pei Wang; Shu-jie Wang; Hong-zheng Bi; Li-rong Zhang; Quan-cheng Kan (European Journal of Clinical Pharmacology, 2017)

Inoculation with endophytic Bacillus megaterium H3 increases Cd phytostabilization and alleviates Cd toxicity to hybrid pennisetum in Cd-contaminated aquatic environments - Ya Li; Hui Han; Lin Yan He; Qi Wang; Xia Fang Sheng (Environmental Science and Pollution Research, 2017)

Erratum to: Chryseobacterium zhengzhouense sp. nov., isolated from groundwater of a well in a vegetable field - Ya-Nan Wang; Wei-Hong He; Ming-Li An; Wen-Yu Tian; Xiao-Yan You; Fang-Qing Ying; Jing Guo; Tao Gong (Antonie van Leeuwenhoek, 2017)

Microsatellite records for volume 8, issue 4 - Alejandra Paola Ojeda; Alexandre Wagner Silva Hilsdorf; Ana Caroline Leite; Ao-ao Yang; Ayako Izuno; Chongbo He; Chun-ya Zhou; Daisuke Kyogoku; Danilo Caneppele; Dongmei Zhu; Fernando Stopato da Fonseca; Hao Yin; et al. (Conservation Genetics Resources, 2016)

Aneuploid progenies of triploid hybrids between diploid and tetraploid loach Misgurnus anguillicaudatus in China - Ya-Juan Li; Yang-Chun Gao; He Zhou; Hai-Yan Ma; Zhong-Qiao Lin; Tian-Yu Ma; Yi Sui; Katsutoshi Arai (Genetica, 2016)

Chryseobacterium zhengzhouense sp. nov., isolated from groundwater of the well in a vegetable field, and emended description of the genus Chryseobacterium - Ya-Nan Wang; Wei-Hong He; Ming-Li An; Wen-Yu Tian; Xiao-Yan You; Fang-Qing Ying; Jing Guo; Tao Gong (Antonie van Leeuwenhoek, 2016)

Inhibition of IRF3 expression reduces TGF-β1-induced proliferation of hepatic stellate cells - Ming-ming Ni; Tao Xu; Ya-rui Wang; Ying-hua He; Qun Zhou; Cheng Huang; Xiao-ming Meng; Jun Li (Journal of Physiology and Biochemistry, 2016)

Effect of fish oil supplement in maintenance hemodialysis patients: a systematic review and meta-analysis of published randomized controlled trials - Lei He; Meng-si Li; Mei Lin; Tian-ya Zhao; Ping Gao (European Journal of Clinical Pharmacology, 2016)

Genomic characteristics of coxsackievirus A8 strains associated with hand, foot, and mouth disease and herpangina - Long Chen; Hong Yang; Chao Wang; Xiang-Jie Yao; Hai-Long Zhang; Ren-Li Zhang; Ya-Qing He (Archives of Virology, 2016)

The roles of methanogens and acetogens in dechlorination of trichloroethene using different electron donors - Li-Lian Wen; Yin Zhang; Ya-Wei Pan; Wen-Qi Wu; Shao-Hua Meng; Chen Zhou; Youneng Tang; Ping Zheng; He-Ping Zhao (Environmental Science and Pollution Research, 2015)

Subcellular distribution and chemical forms of cadmium in a dark septate endophyte (DSE), Exophiala pisciphila - Fangdong Zhan; Yongmei He; Yuan Li; Tao Li; Yun-Ya Yang; Gurpal S. Toor; Zhiwei Zhao (Environmental Science and Pollution Research, 2015)

Declined soil suppressiveness to Fusarium oxysporum by rhizosphere microflora of cotton in soil sickness - Xiaogang Li; Ya’nan Zhang; Changfeng Ding; Zhongjun Jia; Zhili He; Taolin Zhang; Xingxiang Wang (Biology and Fertility of Soils, 2015)

Identification and characterization of naturally occurring DSF ‐family quorum sensing signal turnover system in the phytopathogen X anthomonas - Lian Zhou; Xing‐Yu Wang; Shuang Sun; Li‐Chao Yang; Bo‐Le Jiang; Ya‐Wen He (Environmental Microbiology, 2015)
Summary Molecules of the diffusible signal factor ( DSF )‐family are a class of quorum sensing ( QS ) signals used by the phytopathogens X anthomonas . Studies during the last decade have outlined how X anthomonas cells enter the QS phase. However, information on the mechanism underlying its exit from the QS phase is limited. RpfB has recently been reported as a fatty acyl‐ CoA ligase ( FCL ) that activates a wide range of fatty acids to their CoA esters in vitro . Here, we establish an improved quantification assay for DSF ‐family signals using liquid chromatography‐mass spectrometry in X . campestris pv. campestris ( X cc ). We first demonstrated that RpfB represents a naturally occurring DSF ‐family signal turnover system . RpfB effectively turns over DSF ‐family signals DSF and BDSF in vivo . RpfB FCL enzymatic activity is required for DSF and BDSF turnover. Deletion of rpf B slightly increased X cc virulence in the C hinese radish and overexpression of rpf B significantly decreased virulence. We further showed that the expression of rpf B is growth phase‐dependent, and its expression is significantly enhanced when X cc cells enter the stationary phase. DSF regulates rpf B expression in a concentration‐dependent manner. rpf B expression is also negatively regulated by the DSF signalling components RpfC , RpfG and C lp. The global transcription factor C lp directly binds to the AATGC ‐tgctgc‐ GCATC motif in the promoter region of rpf B to repress its expression. Finally, RpfB ‐dependent signal turnover system was detected in a wide range of bacterial species, suggesting that it is a conserved mechanism.

Retraction Note to: Genetic polymorphisms in the CYP1A1 and CYP1B1 genes and susceptibility to bladder cancer: a meta-analysis - Yan-Zhi Chen; Jing Li; Yu-Xia Zhao; Dan Liu; He-Tong Wang; Ya Gao; Ying Chen (Molecular Biology Reports, 2015)

Meiotic chromosome configurations in triploid progeny from reciprocal crosses between wild-type diploid and natural tetraploid loach Misgurnus anguillicaudatus in China - Ya-Juan Li; Yang-Chun Gao; He Zhou; Hai-Yan Ma; Jia-Qi Li; Katsutoshi Arai (Genetica, 2015)

Helicobacter pylori with the Intact dupA Cluster is more Virulent than the Strains with the Incomplete dupA Cluster - Ming-yi Wang; Chen Shao; Jie Li; Ya-Chao Yang; Shao-bo Wang; Jun-ling Hao; Chun-mei Wu; Xiao-zhong Gao; Shi-he Shao (Current Microbiology, 2015)

Association between the CYP1A2 polymorphisms and risk of cancer: a meta-analysis - Wen-Xia Sun; Ying-Hua Chen; Zhi-Zhong Liu; Jian-Jun Xie; Wei Wang; Ya-Ping Du; Yu Chen; Xu-Liang Shen; Xiao-Feng He; Li-Xia Wu; Wu Wei; Lin Zhang (Molecular Genetics and Genomics, 2015)

Neurochemical properties of the synapses between the parabrachial nucleus-derived CGRP-positive axonal terminals and the GABAergic neurons in the lateral capsular division of central nucleus of amygdala - Ya-Cheng Lu; Yan-Zhou Chen; Yan-Yan Wei; Xiao-Tao He; Xia Li; Wei Hu; Yuchio Yanagawa; Wen Wang; Sheng-Xi Wu; Yu-Lin Dong (Molecular Neurobiology, 2015)

Study of the genomic constitution of the German mirror carp - Ya-Juan Li; Bo Liu; He Zhou; Yang-Chun Gao; Min Gao; Yu-Sheng Wang; Ding-Chen Cao; Xiao-Wen Sun (Aquaculture International, 2015)

Methylopila henanense sp. nov., a novel methylotrophic bacterium isolated from tribenuron methyl-contaminated wheat soil - Ya-Nan Wang; Wen-Yu Tian; Wei-Hong He; Guo-Can Chen; Ming-Li An; Bin Jia; Li Liu; Yang Zhou; Shuang-Jiang Liu (Antonie van Leeuwenhoek, 2015)

Tolerance and Antioxidant Response of a Dark Septate Endophyte (DSE), Exophiala pisciphila, to Cadmium Stress - Fangdong Zhan; Yongmei He; Tao Li; Yun-ya Yang; Gurpal S. Toor; Zhiwei Zhao (Bulletin of Environmental Contamination and Toxicology, 2015)

Lipopolysaccharides Upregulate Hepcidin in Neuron via Microglia and the IL-6/STAT3 Signaling Pathway - Zhong-Ming Qian; Xuan He; Tuo Liang; Ka-Chun Wu; Yik-Chun Yan; Li-Na Lu; Guang Yang; Qian Qian Luo; Wing-Ho Yung; Ya Ke (Molecular Neurobiology, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Molecular cytogenetic study of genome ploidy in the German mirror carp Cyprinus carpio - Ya-Juan Li; Yang-Chun Gao; He Zhou; Bo Liu; Min Gao; Yu-Sheng Wang; Xiao-Wen Sun (Fisheries Science, 2014)

An adaptive noise attenuation method for edge and amplitude preservation - Han-Peng Cai; Zhen-Hua He; Ya-Lin Li; Guang-Ming He; Wen Zou; Dong-Jun Zhang; Pu Liu (Applied Geophysics, 2014)

RETRACTED ARTICLE: Genetic polymorphisms in the CYP1A1 and CYP1B1 genes and susceptibility to bladder cancer: a meta-analysis - Yan-Zhi Chen; Jing Li; Yu-Xia Zhao; Dan Liu; He-Tong Wang; Ya Gao; Ying Chen (Molecular Biology Reports, 2014)

Identification of a putative cognate sensor kinase for the two‐component response regulator HrpG , a key regulator controlling the expression of the hrp genes in X anthomonas campestris pv. campestris - Rui‐Fang Li; Guang‐Tao Lu; Lei Li; Hui‐Zhao Su; Guo‐fang Feng; Ya Chen; Yong‐Qiang He; Bo‐Le Jiang; Dong‐Jie Tang; Ji‐Liang Tang (Environmental Microbiology, 2014)
Summary The bacterial phytopathogen X anthomonas campestris pv. campestris ( Xcc ) relies on the hrp (hypersensitive response and pathogenicity) genes to cause disease and induce hypersensitive response ( HR ). The hrp genes of bacterial phytopathogens are divided into two groups. Xcc hrp genes belong to group II . It has long been known that the group II hrp genes are activated by an AraC ‐type transcriptional regulator whose expression is controlled by a two‐component system ( TCS ) response regulator (named HrpG in Xcc ). However, no cognate sensor kinase has yet been identified. Here, we present evidence showing that the Xcc open‐reading frame XC _3670 encodes a TCS sensor kinase (named HpaS ). Mutation of hpaS almost completely abolished the HR induction and virulence. Bacterial two‐hybrid and protein pull‐down assays revealed that HpaS physically interacted with HrpG . Phos‐tag™ SDS‐PAGE analysis showed that mutation in hpaS reduced markedly the phosphorylation of HrpG in vivo . These data suggest that HpaS and HrpG are most likely to form a TCS . We also showed that XC _3669 (named hpaR2 ), which is adjacent to hpaS and encodes a putative TCS response regulator, is required for full virulence but not HR induction. HpaR2 also physically interacted with HpaS , suggesting that HpaS may also form another TCS with HpaR2 .

New megastigmane glycoside and alkaloids from Streptomyces sp. YIM 63342 - Xue-Qiong Yang; Ya-Bin Yang; Hao Zhou; Guang-Wei He; Li-Xing Zhao; Li-Hua Xu; Zhong-Tao Ding (Natural Product Research, 2013)

Astrocyte-Derived Sonic Hedgehog Contributes to Angiogenesis in Brain Microvascular Endothelial Cells via RhoA/ROCK Pathway After Oxygen–Glucose Deprivation - Quan-Wei He; Yuan-Peng Xia; Sheng-Cai Chen; Yong Wang; Ming Huang; Yan Huang; Jian-Yong Li; Ya-Nan Li; Yuan Gao; Ling Mao; Yuan-Wu Mei; Bo Hu (Molecular Neurobiology, 2013)

Persistence and intergenerational transmission of differentially expressed genes in the testes of intracytoplasmic sperm injection conceived mice - Li-ya Wang; Ning Wang; Fang Le; Lei Li; Le-jun Li; Xiao-zhen Liu; Ying-ming Zheng; Hang-ying Lou; Xiang-rong Xu; Xiao-ming Zhu; Yi-min Zhu; He-feng Huang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Four new species of Entoloma s.l. (Agaricales) from southern China - Xiao-Lan He; Tai-Hui Li; Zi-De Jiang; Ya-Heng Shen (Mycological Progress, 2012)

A new convenient technique for making cell blocks - Qing-Lian He; Ya-Zhen Zhu; Guang-Juan Zheng; Ling-Chun Shi; Shao-Wei Hu; Chu-Tian Li (Cell and Tissue Research, 2012)

Association of 10q23 with colorectal cancer in a Chinese population - Fen-Xia Li; Xue-Xi Yang; Xuan-Qiu He; Ni-Ya Hu; Ying-Song Wu; Ming Li (Molecular Biology Reports, 2012)

Pseudomonas nitritireducens sp. nov., a nitrite reduction bacterium isolated from wheat soil - Ya-Nan Wang; Wei-Hong He; Hua He; Xun Du; Bin Jia; Zhi-Peng Zeng; Ming-Li An; Guo-Can Chen (Archives of Microbiology, 2012)

Characterization and virus susceptibility of a skin cell line from red-spotted grouper (Epinephelus akaara) - Xiao-Ying Lei; Zhong-Yuan Chen; Li-Bo He; Chao Pei; Xiu-Ping Yuan; Qi-Ya Zhang (Fish Physiology and Biochemistry, 2012)

Polymorphisms in the XPG gene and risk of gastric cancer in Chinese populations - Jing He; Li-Xin Qiu; Meng-Yun Wang; Rui-Xi Hua; Ruo-Xin Zhang; Hong-Ping Yu; Ya-Nong Wang; Meng-Hong Sun; Xiao-Yan Zhou; Ya-Jun Yang; Jiu-Cun Wang; Li Jin; et al. (Human Genetics, 2012)

Genetic and physical mapping of qHY-8, a pleiotropic QTL for heading date and yield-related traits in rice - Hai-Ya Cai; Shu Diao; Yong-Gang He; Li-Pan Zhang; Shao-Jia Liu; Ying-Guo Zhu; Zhi-Hong Zhang (Euphytica, 2012)

Characterization of acute renal allograft rejection by proteomic analysis of renal tissue in rat - Gang Chen; Jing-bin Huang; Jie Mi; Yun-feng He; Xiao-hou Wu; Chun-li Luo; Si-min Liang; Jia-bing Li; Ya-xiong Tang; Jie Li (Molecular Biology Reports, 2012)

Molecular cloning and tissue expression of the fatty acid-binding protein (Es-FABP9) gene in the reproduction seasons of Chinese mitten crab, Eriocheir sinensis - Wei-Wei Li; Xing-Kun Jin; Lin He; Ya-Nan Gong; Hui Jiang; Qun Wang (Molecular Biology Reports, 2011)

Normal epigenetic inheritance in mice conceived by in vitro fertilization and embryo transfer - Lei Li; Fang Le; Li-ya Wang; Xiang-rong Xu; Hang-ying Lou; Ying-ming Zheng; Jiang-zhong Sheng; He-feng Huang; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2011)

Norovirus Gastroenteritis Outbreak is Associated with Contaminated Drinking Water in South China - Ya-Qing He; Han-Wu Ma; Xiang-Jie Yao; Qing-Lan Bu; Hong Yang; Wei Huang; Yong-Xiang Duan; Hai-Long Zhang; Chuan-Wen Dai; Wei-Ke Li; Shou-Yi Yu (Food and Environmental Virology, 2010)

A new 3,4-seco-lupane-type triterpenoid from the pulp of Acanthopanax senticosus (Rupr. et Maxim) Harms - Zhao-Wei Yan; Jin-Ping Liu; Dan Lu; Paul Groundwater; Chun-Yan He; Ping-Ya Li (Natural Product Research, 2010)

Post-conditioning protects cardiomyocytes from apoptosis via PKCε-interacting with calcium-sensing receptors to inhibit endo(sarco)plasmic reticulum–mitochondria crosstalk - Shiyun Dong; Zongyan Teng; Fang-hao Lu; Ya-jun Zhao; Hulun Li; Huan Ren; He Chen; Zhen-wei Pan; Yan-jie Lv; Bao-feng Yang; Ye Tian; Chang-qing Xu; et al. (Molecular and Cellular Biochemistry, 2010)

Multilayered polyelectrolyte-coated gold nanorods as multifunctional optical contrast agents for cancer cell imaging - Li-li Chen; Li Jiang; Ya-lun Wang; Jun Qian; Sailing He (Journal of Zhejiang University-SCIENCE B, 2010)

Application of High Energy Dynamic Compaction in Coastal Reclamation Areas - Shi-Jin Feng; Wei-Hou Shui; Li-Ya Gao; Li-Jun He (Marine Georesources & Geotechnology, 2010)

Field studies of the effectiveness of dynamic compaction in coastal reclamation areas - Shi-Jin Feng; Wei-Hou Shui; Li-Ya Gao; Li-Jun He; Ke Tan (Bulletin of Engineering Geology and the Environment, 2010)

Insights into the Substrate Specificity, Inhibitors, Regulation, and Polymorphisms and the Clinical Impact of Human Cytochrome P450 1A2 - Shu-Feng Zhou; Li-Ping Yang; Zhi-Wei Zhou; Ya-He Liu; Eli Chan (The AAPS Journal, 2009)

Ectopic overexpression of AtHDG11 in tall fescue resulted in enhanced tolerance to drought and salt stress - Ya-Jun Cao; Qiang Wei; Yang Liao; He-Ling Song; Xian Li; Cheng-Bin Xiang; Ben-Ke Kuai (Plant Cell Reports, 2009)

Simultaneous detection of human enterovirus 71 and coxsackievirus A16 in clinical specimens by multiplex real-time PCR with an internal amplification control - Xing-Long Xiao; Ya-Qing He; Yi-Gang Yu; Hong Yang; Gu Chen; Hui-Fang Li; Jing-Wei Zhang; Dong-Mei Liu; Xiao-Feng Li; Xiao-Quan Yang; Hui Wu (Archives of Virology, 2009)

Gender-specific associations between MICA-STR and nasopharyngeal carcinoma in a southern Chinese Han population - Wei Tian; Xiao-min Zeng; Li-xin Li; He-kun Jin; Qi-zhi Luo; Fan Wang; Shi-shi Guo; Ya Cao (Immunogenetics, 2006)

Development of a Latex Agglutination Test Using The Major Epitope Domain of Glycoprotein E of Pseudorabies Virus Expressed in E. coli to Differentiate Between Immune Responses in Pigs Naturally Infected or Vaccinated with Pseudorabies Virus - Tang Yong; Chen Huan-chun; Xiao Shao-bo; Qin Ya-li; He Qi-gai; Ren Yu-qi (Veterinary Research Communications, 2005)

Variations of stomatal density and carbon isotope values of Picea crassifolia at different altitudes in the Qilian Mountains - Wei-ya Qiang; Xun-ling Wang; Tuo Chen; Hu-yuan Feng; Li-zhe An; Yuan-qin He; Gang Wang (Trees, 2003)

Ri-mediated transformation of Artemisia annua with a recombinant farnesyl diphosphate synthase gene for artemisinin production - Da-Hua Chen; Chang-Jun Liu; He-Chun Ye; Guo-Feng Li; Ben-Ye Liu; Yu-Ling Meng; Xiao-Ya Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)